Unveiling crosstalk regulations within the polyamine pathway and between polyamine and purine pathways in Aedes aegypti females - Jun Isoe; Thomas D. Horvath; Vlad Orlovsky; Paula Castillo Bravo; Stacy Mazzalupo; Patricia Y. Scaraffia (Insect Biochemistry and Molecular Biology, 2026)

Diversity assessment of gastropod larvae assemblage at two ecoregions of the Greater Caribbean - F.E. Hernández-Perea; A.I. Muñiz-Castillo; O. Gros; H. Oxenford; D. Aldana-Aranda (Regional Studies in Marine Science, 2026)

Resolving polymeric nanoplastics in human cumulus cells by synchrotron X-ray fluorescence and light nano-imaging - Sara Bozzer; Cristina Tufoni; Murielle Salomé; Francesco D’Amico; Clément Holé; Alessandra Gianoncelli; Stefania Luppi; Hiram Castillo Michel; Marine Cotte; Giuseppe Ricci; Lorella Pascolo (Journal of Hazardous Materials, 2026)

Climate change vulnerability of the Afrotemperate flora on Africa’s tropical sky islands - Elvira Castillo-Almansa; Rubén G. Mateo; Mercè Galbany-Casals; Carme Blanco-Gavaldà; Lucía D. Moreyra; Cristina Roquet; Christian Brochmann; Abel Gizaw; Desalegn Chala; Alfonso Susanna; Juan A. Calleja (Biodiversity and Conservation, 2026)
Climate change poses a significant threat to the Afrotemperate flora of the Eastern Afromontane Biodiversity Hotspot, particularly to species confined to high-elevation ecosystems such as those found on the African sky islands. This study evaluates the vulnerability of tropical Afroalpine and Afromontane Helichrysum taxa (Compositae) by assessing their climatic niches and predicting future shifts in distribution, range fragmentation, and altitudinal limits under climate change scenarios. Occurrence records for 14 taxa (eight Afroalpine and six Afromontane) were obtained from recent field campaigns, biodiversity databases and herbaria. Ensemble ecological niche models were developed combining Generalized Linear Models, Generalized Boosting Models, and Random Forest. Taxon-specific bioclimatic variables were selected after correlation analyses. The models were calibrated using current climate data and projected using the PSL-CM6A-LR and MRI-ESM2.0 climate models with both low- and high-emission scenarios. The results show that most Afrotemperate taxa currently occupy only a portion of their climatically suitable habitat, often in geographically distant areas. Future projections indicate significant range contractions and increased fragmentation. Afroalpine taxa could lose 50–66% of their suitable habitat, while Afromontane taxa could decline by 53–79%. Suitable areas were estimated to shift upwards in elevation, with limited potential for colonization of new areas, and with no significant latitudinal or longitudinal shifts. These findings represent the first continental-scale assessment of the impact of climate change on the Afrotemperate flora using ecological niche modelling. The projected climate-induced range losses and increased habitat fragmentation, in particular combined with increasing anthropogenic pressure in this region, highlight the urgent need for targeted conservation actions.

Methoxyacetic acid exposure in rats induces N-butyrylglycinuria consistent with beta-oxidation impairment - Samuele Sala; Janonna Kadyrov; Andres Bernal; Andres M. Castillo; Preechaya Naraprasertkul; Nadia Paesalasakul; Proud Bekanan; Issariya Dhitsuwon; Thanaporn Kulthawatsiri; Reika Masuda; Manthan Sharma; Jutarop Phetcharaburanin; et al. (Archives of Toxicology, 2026)

Confirmed Outbreaks of Streptococcosis Caused by Streptococcus agalactiae Serotype Ia in Nile Tilapia Culture From Campeche, Mexico - R. A. Avila‐Castillo; R. E. del Rio‐Rodriguez; S. A. Soto‐Rodriguez; J. Navarro‐Flores; A. D. Cu‐Escamilla; F. I. Marrujo‐Lopez; K. G. Aguilar‐Rendon; M. I. Gomez‐Solano (Journal of Fish Diseases, 2026)
Streptococcus agalactiae was confirmed as the etiologic agent of streptococcosis in Nile tilapia ( Oreochromis niloticus ) from Campeche, Mexico, during a cross‐sectional investigation of eight semi‐intensive farms (2021–2022) that yielded virulent strains in a challenge assay. Standard bacteriology, histopathology, API‐20 Strep phenotyping, one‐step PCR, and real‐time PCR confirmed S. agalactiae in five farms (62.5%). Gross and histological lesions were characterised by mid‐axial and peduncular muscle abscesses, extensive myonecrosis, granuloma formation, polyserositis, and occasional suppurative meningitis. Experimental infections fulfilled Koch's postulates. Juveniles of O. niloticus (20 g) infected with strain ASG‐2290 at 10 6 CFU/mL produced 53% mortality at 96 h. Whole‐genome sequencing of the strains ASG‐2290 and ASG‐2292 identified them as S. agalactiae Ia, marking the first report of this serotype isolated from farmed tilapia in Mexico. Frequent interstate fry movements are likely to be a risk factor for pathogen dissemination. These findings document the geographic expansion of pathogenic S. agalactiae into the Yucatan Peninsula, underscoring the need for strengthened surveillance, biosecurity, and diagnostic capacity to mitigate economic losses in Mexican tilapia aquaculture. Considering that tilapia aquaculture is carried out all year‐round in the Yucatan Peninsula, the implications of these findings are of major concern.

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

In search of an effective and safe anesthetic in decapod crustaceans: Insights from Procambarus clarkii - I. Ruiz-Jarabo; L. Herrera-Castillo; D. Madera; N. Saiz; E. Isorna; M.J. Delgado; N. de Pedro (Aquaculture, 2026)

Ensuring adaptability and applicability of long-term contaminant monitoring initiatives: A discussion of NOAA’s National Mussel Watch Program current practices and future approaches - N. A. Castillo; L. M. Swam-Jaramillo; M. M. Rider; A. Morozova; K. L. Kimbrough; E. D. Davenport; M. A. Edwards; F. Arzayus; D. A. Apeti (Environmental Monitoring and Assessment, 2026)

Traumatic Marjolin’s ulcer in sheep: Squamous cell carcinoma arising from chronic dorsal fence-wire injuries - Telma Sousa Lima; Francisco das Chagas Sarmento Júnior; Francisca Maria Sousa Barbosa; Elizandra Teixeira Melo; Silvio Miguel Castillo; Harlan Hallamys Lima Nascimento; Glaucia D. Kommers; Ricardo Barbosa Lucena (The Veterinary Journal, 2026)

Revisiting Strategies for Bacterial Enumeration: The Case for Viable but Nonculturable (VBNC) Cells in Supplement Products - T. O. Kirby; J. R. Townsend; E. D. Walts; A. Kiefer; J. Zhu; M. Cormier; D. Pathak; C. Wong; A. Castillo; J. Ochoa-Repáraz; R. Jäger; R. H. Lai; et al. (Probiotics and Antimicrobial Proteins, 2026)

Multi-tissue contamination (mercury, lead, and organochlorine pesticides) and health biomarkers in Northern Shoveler and Northern Pintail during wintering - Sarahi Roos-Muñoz; Edgar Cruz-Acevedo; Jose Alfredo Castillo-Guerrero; Olivia Torres-Bugarin; Oscar Basilio del Río-Zaragoza; Jaqueline García-Hernandez; Gabriela Aguilar-Zarate; Gustavo D. Danemann; Miguel Betancourt-Lozano (Environmental Management, 2026)

The IPBES invasion-management framework supports informed decision-making for managing biological invasions - Chika Egawa; K. V. Sankaran; Andy W. Sheppard; Evangelina Schwindt; Llewellyn C. Foxcroft; Sonia Vanderhoeven; Lora Peacock; Maria L. Castillo; Rafael D. Zenni; Jana Müllerová; Ana Isabel González Martínez; John K. Bukombe; et al. (Biological Invasions, 2026)
The Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) Thematic Assessment Report on Invasive Alien Species and Their Control presents a “conceptual diagram of management-invasion continuum”, introducing a versatile framework to support decision-making on the management of biological invasions. Drawing on an extensive synthesis of current knowledge, this IPBES invasion-management framework has been developed to broaden the scope of existing invasion curves—which primarily overlay generic management objectives onto a sigmoid curve depicting the expansion of the affected area over time—and to illustrate the applicability of the concept of effective management at different stages of the biological invasion process. To introduce the IPBES invasion-management framework to a wider audience, this paper explains the features of the framework and defines the invasion-stage-based management approaches and the potential outcomes envisaged therein. Reflecting the currently limited management options for biological invasions in marine and other connected-water systems, unlike in terrestrial and closed-water systems, the IPBES invasion-management framework clearly distinguishes between these two groups of systems. For each, it presents management approaches including three key factors that decision-makers should consider concurrently: management objectives, targets, and actions. This framework supports informed decision-making in the management of biological invasions in all ecosystems.

Formulation and evaluation of a functional beverage from Ilex guayusa Loes. (Aquifoliaceae): Chemical analysis, antioxidant activity, and sensory acceptance - Luis G. Sequeda-Castañeda; Laura D. Bermeo-Pulido; Yineth Piñeros-Castro; Geison M. Costa; Yuri M. Castillo-Quiroga (Food and Humanity, 2026)

Carpobrotus taxa benefit more from clonal integration in their non-native than native ranges - Marta Pérez-Diz; Hana Skálová; Susan Canavan; María Loreto Castillo; Paula Gervazoni; Luís González; Petr Pyšek; Jonatan Rodríguez; Kateřina Štajerová; Giuseppe Brundu; Carla M. D’Antonio; Tom Dudley; et al. (Biological Invasions, 2026)
Understanding physiological integration in invasive clonal plants is relevant to invasion biology because resource transfer across ramets may allow alien plants to buffer spatial heterogeneity in their introduced areas. However, experimental evidence across native and non-native ranges is limited. Here, we tested whether physiological integration provides greater performance benefits to Carpobrotus taxa in non-native than native ranges. We grew clonal fragments under controlled conditions from eleven populations representing different genetic clusters across their native and non-native ranges. Connected recipient ramets showed higher growth than severed ones, with increased ramet length, node number, Branching and Vigor Indices, while connected donor ramets showed reduced growth, indicating resource redistribution within the clone. Plants from non-native ranges exhibited overall higher growth-related traits and chlorophyll content, suggesting enhanced growth and stress tolerance across genetic backgrounds. These results indicate that physiological integration allows Carpobrotus taxa to overcome environmental heterogeneity by reallocating resources among ramets, promoting clonal growth and expansion, and potentially increasing competitive ability in non-native ranges. Our findings provide experimental evidence across multiple populations that physiological integration can promote the ecological success of clonal invaders.

Cap and stipe extracts from Pleurotus ostreatus mushrooms reveal differences in enhancing the quality and stability of beef burgers during frozen storage - Milagros Maribel Coaguila Gonza; Juan D. Rios-Mera; Alan Giovanini de Oliveira Sartori; Chimenes Leal de Araújo; Sarah Mafeis de Jesus; Nils Leander Huamán-Castilla; Erick Saldaña; Carmen Josefina Contreras Castillo (Meat Science, 2026)

Strengthening national genebanks through genomics and regional collaboration: Lessons from Latin America and the Caribbean - M. Carvajal-Yepes; C. Petroli; M. Correa; F. Breseghello; G. Tapia; E. Salazar; A. Chassaigne; M. Ferreyra; P.H. Reyes-Herrera; M. Guzmán; A. Mendoza; R. Vidal; et al. (Global Food Security, 2026)

Environmental Gradients Decouple Demographic and Adaptive Connectivity in a Highly Mobile Coastal Marine Species - Chris J. Brauer; Andrea Bertram; Jonathan Sandoval‐Castillo; Anthony Fowler; Justin D. Bell; Paul Hamer; Maren Wellenreuther; Luciano B. Beheregaray (Molecular Ecology, 2026)
Understanding how eco‐evolutionary processes shape genetic variation and persistence in marine species with highly variable recruitment dynamics and dispersal potential remains a fundamental challenge, particularly when considering the interplay between gene flow and local adaptation. Here, we employed a seascape genomics approach to investigate population connectivity and local adaptation in Australasian snapper ( Chrysophrys auratus , Sparidae) along 1500 km of the environmentally heterogeneous southern Australian coastline. Using genome‐wide SNPs, we identified distinct eastern and western regional populations aligned with known biogeographical regions. Genotype‐environment association analyses revealed 855 candidate adaptive loci associated with environmental variation, including temperature, salinity and primary productivity. Connectivity analyses using neutral markers indicated high gene flow within both eastern and western regions, while candidate adaptive loci revealed substantially reduced connectivity, especially for Northern Spencer Gulf and West Coast populations. This contrast implies a decoupling of demographic and adaptive connectivity, in which strong environmental gradients appear to reduce the effective exchange of adaptive variation despite high overall connectivity. Our results support contingent migration as a potential mechanism modulating the balance between local adaptation and gene flow in this economically and ecologically important marine species. These findings might also have implications for regional management of other coastal fisheries that are experiencing substantial declines. As climate change alters coastal marine environments around the world, the dynamics of local recruitment, site fidelity and local adaptation are expected to change. This highlights the importance of integrating knowledge about eco‐evolutionary processes into marine resource management, fisheries stock assessment, and restocking and stock enhancement activities.

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Low-dose tamoxifen ameliorates ovariectomy-induced metabolic and immune dysfunction - Heather E. McClurg; Amanda Ferraro; Gina Pham; Itzel Morales-Hernandez; Estefania Valencia-Rincon; Kevin D. Pham; Willard M. Freeman; Jacquelyn A. Gorman; Marisol Castillo-Castrejon (GeroScience, 2026)
The decline in estrogen following menopause is a major driver of metabolic and immune dysfunction in aging females. While hormone replacement therapy improves many of these outcomes, its clinical use remains limited due to concerns regarding estrogen-sensitive malignancies. Tissue-selective estrogen complexes (TSECs), which combine estrogens with selective estrogen receptor modulators (SERMs) such as tamoxifen (TAM), represent a promising strategy to preserve the metabolic and immunological benefits of estrogen while reducing oncogenic risk. However, the systemic effects of TAM under conditions of estrogen deficiency remain incompletely defined. In this study, we investigated the metabolic and immunomodulatory actions of low-dose TAM, alone or in combination with 17β-estradiol (E2), in adult ovariectomized (OVX) female mice. OVX resulted in increased adiposity, hepatic steatosis, glucose intolerance, insulin resistance, immunoglobulin G3 (IgG3) concentration, and systemic inflammation, along with decreased immunoglobulin G1 (IgG1) concentration. E2, TAM, and E2 + TAM each attenuated OVX-induced adipose expansion, adipocyte hypertrophy, and proinflammatory cytokine production. TAM improved insulin sensitivity but did not fully restore glucose tolerance. Transcriptomic analysis of visceral adipose tissue-resident B cells revealed that E2 and E2 + TAM modulate overlapping yet distinct immune-regulatory networks, including suppression of pro-inflammatory signaling, regulation of immune checkpoints, and genes linked to adipose homeostasis. Low-dose TAM emerges as a modulator of estrogen receptor signaling that attenuates multiple features of OVX-induced metabolic and inflammatory dysfunction, though its limited effect on glycemic control highlights the need for tissue-specific evaluation of SERM-based interventions. These findings provide mechanistic insight into endocrine–immune–metabolic interactions and inform strategies to reduce aging-related disease risk in postmenopausal women. Graphical Abstract Created in BioRender ( https://BioRender.com/7ouhlqq ), Castillo M. (2025)

Spatio-temporal performance of 2D local inertial hydrodynamic models for urban drainage and dam-break applications - Marcus N. Gomes Jr.; Maria A.R.A. Castro; Luis M.R. Castillo; Mateo H. Sánchez; Marcio H. Giacomoni; Rodrigo C.D. de Paiva; Paul D. Bates (Journal of Hydrology, 2026)

Fermentation of rice milling by-products can completely replace soybean meal in the diet of Oreochromis niloticus fingerlings - Mark Henry F. De Leon; Dinah Grace D. Bienes; Mary Jessa Bell B. Pagapulan; Emelyn Joy G. Mameloco; Vyenge Erre D. Gayosa; Fredson H. Huervana; Carmelo S. del Castillo; Rex Ferdinand M. Traifalgar (Frontiers in Marine Science, 2026)
The expansion and intensification of aquaculture have been widely adopted to support large-scale production, creating a reliance on high-protein feed ingredients such as soybean meal (SBM) and fish meal (FM). These ingredients, however, are costly and unsustainable, emphasizing the need for alternative plant-based protein sources for aquafeeds. This study assessed the nutritional and feed value of fermented rice bran meal (FRBM) as a substitute for SBM in the diet of tilapia ( Oreochromis niloticus ) fingerlings. Five diets were formulated with FRBM replacing SBM at 0%, 25%, 50%, 75%, and 100%, and were fed to fingerlings over a 60-day period. Results showed that FRBM could fully replace SBM, with growth-promoting effects particularly observed at 25% replacement. Survival, percentage weight gain, feed conversion ratio (FCR), and specific growth rate (SGR) did not differ significantly among the treatments with varying FRBM levels. No significant differences in carcass composition (protein, lipid, and ash) were observed among tilapia fed with diets containing FRBM replacement. The apparent protein and dry matter digestibility coefficients of FRBM are 91.52% and 66.67%, respectively. Histological examination also revealed no intestinal abnormalities, even at the highest level of FRBM inclusion. Overall, the findings suggest that solid-state fermented rice bran can fully replace soybean meal in the diet of O. niloticus . In addition, its use presents a practical option to help meet the growing protein requirements in aquafeeds and to promote the sustainable expansion of tilapia aquaculture.

Physiological and transcriptomic responses to fasting-refeeding in Arapaima gigas: Insights into compensatory growth for aquaculture production - T.H. Delgadin; L.E. Santos-Rojas; D. Medina-Herrera; N.M. Herrera-Castillo; A.M. Alonso; A. Saavedra-Flores; E.A. López-Landavery; J.I. Fernandino; E. Zelada-Mázmela (Aquaculture, 2026)

Revisiting Small‐Scale Aquaculture ( SSA ) - Liliana Sierra Castillo; Halley E. Froehlich; Jono R. Wilson; Jessica A. Gephart; Erendira Aceves‐Bueno; Steven D. Gaines (Reviews in Aquaculture, 2026)
Aquatic foods are a vital source of nutrition, yet growing demand and stagnant wild‐capture fisheries have positioned aquaculture as essential to meeting global food needs. Despite this, aquaculture's diverse forms remain poorly understood, particularly small‐scale aquaculture (SSA). Unlike small‐scale fisheries (SSF), which are widely recognized in policy and research, SSA lacks consistent definitions and is often conflated with SSF or defined narrowly by physical metrics like farm size. This limits its visibility in policy and development efforts, overlooking critical social, economic, and governance dimensions such as ownership, labor, and market orientation. Through a systematic review of 83 studies across 24 countries, we analyze SSA across ecosystems (freshwater, brackish, marine) and species groups (finfish, invertebrates, seaweed) to identify trends in production characteristics, yield reporting, and social dimensions. We find freshwater SSA dominates the literature, while marine SSA, especially mollusk farming, is significantly underrepresented. SSA exhibits wide variation in yields, farm sizes, ownership, and management structures, indicating that existing classification frameworks are insufficient. We propose a context‐sensitive, social‐ecological classification system that integrates production metrics with governance and socioeconomic characteristics. To guide application, we offer two policy frameworks, one for regions with existing SSA definitions, recommending participatory revision and expanded data collection; and one for regions without definitions, advocating for a stepwise approach to characterization. Our findings underscore the need for more inclusive, adaptable classifications to improve SSA's visibility in global food policy and unlock its full contributions to sustainable development, equity, and local livelihoods.

Functional characterization of splice variants in hereditary breast and ovarian cancer susceptibility genes - Laura Rosado-Jiménez; Younes Mestre-Terkemani; Ángeles García-Aliaga; María D. Sarabia-Meseguer; Miguel Marín-Vera; José A. Macías-Cerrolaza; Pilar Sánchez-Henarejos; María R. García-Hernández; Marta Zafra-Poves; Beatriz C. Álvarez-Abril; Carmen B. López-Sánchez; María P. Moya-Martínez; et al. (Familial Cancer, 2025)

Narrating responses and changes to Diversity, Equity, and Inclusion within nutrition-focused organizations - Shaneice D. Urbina Acevedo; Selina Awinbisa Agandaa; Marie A.K. Allsopp Castillo; Marie K. Fialkowski; Alexandra L. MacMillan Uribe; Kendra OoNorasak; Belkis I. Santiago-Martínez; Dreamal I. Worthen; Ayron Walker (Journal of Nutrition Education and Behavior, 2025)

Early season grazing triggers positive herbivore-plant-soil feedbacks in Festuca paniculata grasslands: A study combining field and satellite data - Miguel Castillo-Garcia; Concepción L. Alados; Fernando Perez-Cabello; Raquel Montorio; José D. Anadón; Federico Fillat; Yolanda Pueyo (Agriculture, Ecosystems & Environment, 2025)

A New Neotropical Species of Gnathostoma (Nematoda: Gnathostomatidae) from the Northern Four-Eyed Opossum Philander vossi (Marsupialia) - M. Á. Mosqueda-Cabrera; E. Sánchez-Miranda; L. D. Castillo-Loeza; G. Torres-Carrera; L. García-Prieto (Acta Parasitologica, 2025)
Purpose This work provides a detailed morphological description of a previously identified but unnamed lineage inside Gnathostoma spp. from Mexico. Methods Specimens of the four-eyed opossum Philader vossi were collected in Tlacotalpan, Veracruz, Mexico. Specimens were examined morphologically using both light microscopy and scanning electron microscopy. Additionally, we generate DNA sequences for the following loci: mitochondrial cox 1 and nuclear 5.8S rRNA and ITS-2 and 28S rDNA. Results The new species, Gnathostoma mexicanum n. sp., differs from G. turgidum Stossich, 1902, the common gnathostomid species infecting Didelphis spp. from the Americas, in its smaller body size, fewer teeth on the cuticular spines at anterior half of body, as well as site of infection (pyloric region vs. stomach layers). Host specificity further distinguishes the two species. Additionally, molecular data show that the new species clearly diverges from its congeners. Conclusions This work represents the fourth Gnathostoma species described for Mexican mammals and the eight recorded in the Americas.

Admixture Increases Genetic Diversity and Adaptive Potential in Australasian Killer Whales - Isabella M. Reeves; John A. Totterdell; Jonathan Sandoval‐Castillo; Emma L. Betty; Karen A. Stockin; Ramari Oliphant Stewart; Muriel Johnstone; Andrew D. Foote (Molecular Ecology, 2025)
Admixture is the exchange of genetic variation between differentiated demes, resulting in ancestry within a population coalescing in multiple ancestral source populations. Low‐latitude killer whales ( Orcinus orca ) populations typically have higher genetic diversity than those in more densely populated, high productivity and high‐latitude regions. This has been hypothesized to be due to episodic admixture between populations with distinct genetic backgrounds. We test this hypothesis by estimating variation in local ancestry of whole genome sequences from three genetically differentiated, low‐latitude killer whale populations and comparing them to global genetic variation. We find ‘Antarctic‐like’ ancestry tracts in the genomes of southwestern Australia (SWA) population including recent (within the last 2–4 generations) admixture. Admixed individuals had, on average, shorter and fewer runs of homozygosity than unadmixed individuals and increased effective population size ( N e ). Thus, connectivity between demes results in the maintenance of N e of relatively small demes at a level comparable to the sum of N e across demes. A subset of the admixed regions was inferred to be evolving under selection in the SWA population, suggesting that this admixed variation may be contributing to the population's adaptive potential. This study provides important and rare empirical evidence that small populations can maintain genetic diversity due to sporadic admixture between different genetic backgrounds and that admixed ancestry can promote the long‐term stability of N e .

Pea protein's interfacial behavior and emulsifying capacity as affected by high-pressure homogenization treatments: an in-depth study with dilatational rheology characterization - Giulia D'Alessio; Julia Maldonado-Valderrama; Teresa del Castillo-Santaella; Annalaura Sabatucci; Antonio Francioso; Paola Pittia; Carla Daniela Di Mattia (Food Hydrocolloids, 2025)

A recently identified mass-transport deposit stack in the Guaymas Basin, Gulf of California (México), and its implication in the basin tectonics - A. Piña; J. Stock; D. Lizarralde; S. Hart; K. Marsaglia; C. Gallegos-Castillo; C. Berndt; A. González-Fernández; C. Mortera-Gutiérrez; A. Martín-Barajas (Marine Geology, 2025)

Aquaculture isn’t always the answer: rethinking blue transitions through justice and community experience - Liliana Sierra Castillo; Caroline E. Ferguson Irlanda; Erendira Aceves-Bueno; Halley E. Froehlich; Cristina Mancilla; Antonella Rivera; Steven D. Gaines (Global Environmental Change, 2025)

Long-Term Treatment with Alcaligenes faecalis A12C Improves Host Resistance to Pathogens in Septic Rats: Possible Contribution of Curdlan-Like Immune Trainer - C. J. Martel-Benítez; R. Alayón-Afonso; D. Padilla Castillo; F. J. Chamizo-López; M. Isabel García-Laorden; A. Espinosa de los Monteros y Zayas; J. C. Rivero-Vera; P. Nogueira Salgueiro; F. Real; A. Bordes-Benítez; A. Martel Quintana; C. Almeida Peña; et al. (Probiotics and Antimicrobial Proteins, 2025)
Curdlan, a β-1,3/1,6-glucan found in Alcaligenes faecalis ( A. faecalis ) wall, activates innate and humoral immunity. The aim of this study is to evaluate whether pretreated rats with A. faecalis A12C could prevent sepsis disturbances and identify the immunomodulatory mechanisms involved. Experiments occurred in two stages: a survival study with 16 rats randomly divided into septic (SC) ( n = 8) and septic pretreated (SA) ( n = 8) groups and 45 rats divided into four groups: healthy (AGUSAN) ( n = 9), septic (AGUIC) ( n = 13), septic pretreated (AGUIA) ( n = 14), and healthy pretreated (AGUSTO) ( n = 9). Sepsis was induced by cecal ligation and puncture after 30 days of A. faecalis A12C pretreatment or without. SA group had a higher survival rate of 58% vs. 16% for SC group ( P < 0.05). Overall, AGUIA showed better status than AGUIC ( P < 0.01). Higher monocytosis was found in AGUIA and AGUSTO vs. AGUIC and AGUSAN, respectively ( P < 0.05). A gradual increase in curdlan fecal concentration was observed in AGUIA during pretreatment. Fecal concentrations of Escherichia coli significantly decreased in AGUIA and AGUSTO. Bacterial load in urine, peritoneal lavage fluid (PLF), and bronchoalveolar lavage fluid (BALF) decreased ( P < 0.05) in AGUIA vs. AGUIC. Finally, lower inflammation was observed in serum, BALF, and PLF, with reduced IL-6, IL-10, IL-1β, and TNF-α, along with less damage in lungs and peritoneum in AGUIA vs. AGUIC. These findings suggest the connection between curdlan—produced by A. faecalis A12C—with the immune system and the reduction in severity of experimental sepsis.

Cardiovascular risk of gender-affirming estrogen therapy in a transgender rat model - D. S. Escudero; V. R. Martínez; Y. Pirosanto; G. A. Colareda; M. Pis Diez; J. M. Lofeudo; O. Castillo; J. O. Vélez Rueda; E. L. Portiansky; N. G. Pérez; R. G. Díaz (Journal of Molecular Medicine, 2025)

Adaptive responses to thinning: Growth and sensitivity to hydric and thermal stress in four widely planted pine species - Àngela Manrique-Alba; Santiago Beguería; J. Julio Camarero; Antonio J. Molina; Gonzalo G. Barberá; Juan A. Blanco; Antonio M. Cachinero-Vivar; Víctor M. Castillo; Antonio D. del Campo; Álvaro Hernández; J. Bosco Imbert; María N. Jiménez; et al. (Agricultural and Forest Meteorology, 2025)

Continuity in phenological monitoring: Assessing the performance of an updated PhenoCam - Mostafa Javadian; Francisco Salgado-Castillo; Koen Hufkens; Andrew D. Richardson (Agricultural and Forest Meteorology, 2025)

From past to present: Shifting landscape drivers of dung beetle functional and phylogenetic diversity in a tropical reserve - José D. Rivera-Duarte; Renato P. Salomão; Eduardo Ulises Castillo-Pérez; Juan José Von Thaden; Alejandro Espinosa de los Monteros; Mario E. Favila (Journal of Environmental Management, 2025)

… and the devil is in the details: A response to Furió et al. (2024) - Vicente D. Crespo; Carolina Castillo (Palaeoworld, 2025)

Source apportionment of PM10 particles in the urban atmosphere using PMF and LPO-XGBoost - Ying Liu; Bowen Jin; Xun Zhang; Xiansheng Liu; Tao Wang; Vy Ngoc Thuy Dinh; Jean-Luc Jaffrezo; Gaëlle Uzu; Pamela Dominutti; Sophie Darfeuil; Olivier Favez; Sébastien Conil; et al. (Environmental Research, 2025)

Effective in vitro bulbification and alkaloid dereplication by GC-MS of Chilean Zephyranthes splendens, an endemic species of the Andes mountains - Ricardo E. Hernández; Jean Paulo de Andrade; Natalia Opazo; Ignacia Castillo; Strahil Berkov; Ariel D. Arencibia (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Productivity and nutritional quality of pastures in a silvopastoral system under two harvest intervals in southeastern Mexico - Benito B. Dzib-Castillo; Fernando Casanova-Lugo; Dixan Pozo-Leyva; Ricardo L. D. Costa; Laura Macario-González; Flavia M. A. Gimenes; Luis A. Lara-Pérez; Alfonso J. Chay-Canul (Agroforestry Systems, 2025)

Different reproductive strategies influence in vitro germination in Chloraea gavilu and Chloraea crispa (Orchidaceae) - G. Pereira; D. Castillo-Novales; O. Jeldes-Cajas; J. T. Otero; C. Arriagada; C. Atala (Brazilian Journal of Botany, 2025)

Histopathological and immunohistochemical characteristics of a thyroglossal duct cyst in a budgerigar (Melopsittacus undulatus) - Reyes Proa-Castillo; Gary García-Espinosa; Mireya Juárez-Ramírez; Saulo I. Cruz-Sánchez; Félix D. Sánchez-Godoy (Journal of Comparative Pathology, 2025)

Comparative study of the physicochemical properties of metal organic frameworks in the adsorption of textile dyes - A. N. Pérez-Jasso; I. A. Aguayo-Villarreal; C. K. Rojas-Mayorga; R. Muñiz-Valencia; D. I. Mendoza-Castillo; A. Bonilla-Petriciolet (International Journal of Environmental Science and Technology, 2025)

Lack of cold temperatures is driving recent high-summer warming in the southern Rocky Mountains - M. C. A. Torbenson; E. Martinez del Castillo; F. Reinig; D. W. Stahle; K. E. King; J. T. Maxwell; G. L. Harley; E. Ziaco; J. Esper (International Journal of Biometeorology, 2025)
We present a 483-year-long tree-ring chronology from a high-elevation Engelmann spruce stand in central Colorado. Over 800,000 density measurements produce a maximum latewood density (MXD) record, which together with tree-ring widths, is used to assess the climatic influences on radial tree growth. Variability in MXD is strongly related to local and regional August maximum temperatures (T max ) for 127 years of overlapping instrumental climate data. A single-predictor reconstruction based on the MXD record explains > 50% of the variance in regional August T max is presented and considered robust for the period 1662–2021. The estimates of past temperature variability display phases of continuous cold conditions that are beyond the range of the instrumental record, including the 1830s. Our results further indicate that August T max have been higher since the early 1990s than for any other 30-year period in the past 350 years. This recent increase occurs on top of multi-centennial warming, and appears to be driven mainly by less frequent cold summers rather than an increase in warm extremes.

Cytomegalovirus Infection Affects the Differentiation and Determines the Functionality of a Human Progenitor Neural Cell Line - H. M. González-Sánchez; E. I. Rubio Hernández; A. S. Silva-Ramírez; A. Miranda-López; A. E. Monsiváis-Urenda; M. Comas-García; D. E. Noyola; V. M. Rodríguez; C. G. Castillo (Current Microbiology, 2025)

Using a vibrating microtome to prepare Mentha × piperita shoot tip sections for live-tissue microscopy experiments - Heidi D. Kreckel; Albert Ochoa-Castillo; Stephanie Villanueva; Gayle M. Volk; Nancy E. Levinger (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

One well-planned and executed exchange is better than two: Lessons learned from a reciprocal fisheries learning exchange between Madagascar and Mexico - Katie R. Thompson; Steve Rocliffe; Alejandro Castillo López; Tinah Martin; S. Hoyt Peckham; Christian Portillo; Xavier Vincke; Lekelia D. Jenkins (Marine Policy, 2025)

Late Holocene climate and environmental change in the Teuchitlán basin, Jalisco, Mexico - Gabriel Vazquez-Castro; Berenice Solis-Castillo; Priyadarsi D. Roy (Quaternary International, 2025)

Six decades of global coral bleaching monitoring: a review of methods and call for enhanced standardization and coordination - Andrea Rivera-Sosa; Aarón Israel Muñiz-Castillo; Ben Charo; Gregory P. Asner; Chris M. Roelfsema; Simon D. Donner; Brianna D. Bambic; Ana Gabriela Bonelli; Morgan Pomeroy; Derek Manzello; Paulina Martin; Helen E. Fox (Frontiers in Marine Science, 2025)
Coral bleaching poses a severe threat to the health and survival of global coral reef ecosystems, with recent events surpassing historical heat stress records. To address this crisis, improved long-term monitoring, communication, and coordination are urgently required to enhance conservation, management, and policy responses. This study reviews global coral bleaching survey methodologies and datasets spanning 1963 to 2022, identifying key challenges in methodological standardization, including database duplication and inconsistencies in naming and reporting bleaching metrics. These issues hinder comparative analyses and contribute to discrepancies in global bleaching impact assessments. We developed a typology of twenty-nine coral bleaching methods used across various scales, encompassing remote sensing tools, underwater surveys, and specimen collection. Analysis of 77,370 observations from three major datasets revealed that 9.36% of entries lacked methodological descriptions. Among recorded methods, belt transects (42%), line and point intercept transects (33%), and random surveys (17%) were the most widely applied. Practitioner surveys underscored the dominance of in situ transect and visual methods, highlighting the growing adoption of photo quadrats—an emerging yet underrepresented technique in existing datasets. To enhance global coral bleaching assessments, we propose a standardized framework that ensures open access and accessible data that aligns with decision-makers’ needs for efficient data aggregation and interoperability to better understand temporal and spatial bleaching events. A globally coordinated coalition should unify protocols, improve data-sharing capabilities, and empower regional networks through targeted training, incentives, and open communication channels. Strengthening field capacity in coral taxonomy and standardized survey methodologies, alongside integrating advanced tools, will improve data quality and comparability. Additionally, creating precise geolocated datasets will bridge on-the-ground observations with advanced remote sensing systems, refining the accuracy of satellite-based early warning tools. Establishing interoperable online platforms will further streamline data integration and accessibility, providing a robust foundation to support global responses to coral bleaching and foster impactful conservation initiatives.

Biome conservatism prevailed in repeated long-distance colonization of Madagascar’s mountains by Helichrysum (Compositae, Gnaphalieae) - Carme Blanco-Gavaldà; Cristina Roquet; Genís Puig-Surroca; Santiago Andrés-Sánchez; Sylvain G. Razafimandimbison; Rokiman Letsara; Nicola Bergh; Glynis V. Cron; Lucía D. Moreyra; Juan Antonio Calleja; Òscar Castillo; Randall J. Bayer; et al. (Molecular Phylogenetics and Evolution, 2025)

Geomorphology of the northern and southern continental margins of the Iberian Peninsula: Quaternary interplay of tectonics and sedimentation - Gemma Ercilla; Jesús Galindo-Zaldívar; Carmen Juan; Ferran Estrada; Jorge Iglesias; Javier Valencia; Víctor Tendero-Salmerón; Elia d'Acremont; María del Carmen Fernández-Puga; Lourdes González-Castillo; Asier Madarieta-Txurruka; Desiree Palomino; et al. (Marine Geology, 2025)

Shortfalls in the protection of Important Shark and Ray Areas undermine shark conservation efforts in the Central and South American Pacific - Théophile L. Mouton; Adriana Gonzalez-Pestana; Christoph A. Rohner; Ryan Charles; Emiliano García-Rodríguez; Peter M. Kyne; Amanda Batlle-Morera; Giuseppe Notarbartolo di Sciara; Asia O. Armstrong; Enzo Acuña; Joanna Alfaro-Shigueto; Randall Arauz; et al. (Marine Policy, 2025)

Widespread pharmaceutical exposure at concentrations of concern for a subtropical coastal fishery: Bonefish (Albula vulpes) - N.A. Castillo; R.O. Santos; W.R. James; R. Rezek; D. Cerveny; R.E. Boucek; A.J. Adams; J. Fick; T. Brodin; J.S. Rehage (Marine Pollution Bulletin, 2024)

Genomic Vulnerability to Climate Change of an Australian Migratory Freshwater Fish, the Golden Perch ( Macquaria ambigua ) - Emily J. Booth; Chris J. Brauer; Jonathan Sandoval‐Castillo; Katherine Harrisson; Meaghan L. Rourke; Catherine R.M. Attard; Dean M. Gilligan; Zeb Tonkin; Jason D. Thiem; Peter J. Unmack; Brenton Zampatti; Luciano B. Beheregaray (Molecular Ecology, 2024)
Genomic vulnerability is a measure of how much evolutionary change is required for a population to maintain optimal genotype‐environment associations under projected climates. Aquatic species, and in particular migratory ectotherms, are largely underrepresented in studies of genomic vulnerability. Such species might be well equipped for tracking suitable habitat and spreading diversity that could promote adaptation to future climates. We characterised range‐wide genomic diversity and genomic vulnerability in the migratory and fisheries‐important golden perch ( Macquaria ambigua ) from Australia's expansive Murray–Darling Basin (MDB). The MDB has a steep hydroclimatic gradient and is one of the world's most variable regions in terms of climate and streamflow. Golden perch are threatened by fragmentation and obstruction of waterways, alteration of flow regimes, and a progressively hotter and drying climate. We gathered a genomic dataset of 1049 individuals from 186 MDB localities. Despite high range‐wide gene flow, golden perch in the warmer, northern catchments had higher predicted vulnerability than those in the cooler, southern catchments. A new cross‐validation approach showed that these predictions were insensitive to the exclusion of individual catchments. The results raise concern for populations at warm range edges, which may already be close to their thermal limits. However, a population with functional variants beneficial for climate adaptation found in the most arid and hydrologically variable catchment was predicted to be less vulnerable. Native fish management plans, such as captive breeding and stocking, should consider spatial variation in genomic vulnerability to improve conservation outcomes under climate change, even for dispersive species with high connectivity.

PM10-bound trace elements in pan-European urban atmosphere - Xiansheng Liu; Xun Zhang; Tao Wang; Bowen Jin; Lijie Wu; Rosa Lara; Marta Monge; Cristina Reche; Jean-Luc Jaffrezo; Gaelle Uzu; Pamela Dominutti; Sophie Darfeuil; et al. (Environmental Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Recruitment niche segregation of halophytes along the tidal gradient - Adolfo F. Muñoz-Rodríguez; María D. Infante-Izquierdo; Alejandro Polo-Ávila; Virgilio Hermoso-López; Francisco J.J. Nieva; Blanca Gallego-Tévar; Jesús M. Castillo (Estuarine, Coastal and Shelf Science, 2024)

Differential tissue distribution of pharmaceuticals in a wild subtropical marine fish - N.A. Castillo; R.O. Santos; W.R. James; R. Rezek; D. Cerveny; R.E. Boucek; A.J. Adams; J. Fick; T. Brodin; J.S. Rehage (Aquatic Toxicology, 2024)

Biodiversity of octopuses in the Americas - Roberto González-Gómez; Otilio Avendaño; Irene de los Angeles Barriga-Sosa; Penélope Bastos; Claudia Caamal-Monsreal; Gabriela Castillo-Estrada; Celso Cedillo-Robles; Adam Daw; Mariana Díaz-Santana-Iturrios; Gabriela Galindo-Cortes; Jürgen Guerrero-Kommritz; Manuel Haimovici; et al. (Marine Biology, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Public policy instruments coherence analysis to address coastal risk in Yucatan, Mexico - L. Vidal-Hernández; A. Cuevas-Jiménez; D. de Yta-Castillo; V.S. Ávila-Foucat; Ileana Espejel (Marine Policy, 2024)

P18-09 Quantitative analysis of micro and nanoplastics in biological tissues: implications for environmental and human health - M. Garcia; A. Nihart; R. Liu; E. El Hayek; E. Castillo; B. Bleske; E. Barrozo; M.A. Suter; J. Scott; K. Forsythe; N. Adolfi; D. Gallego Umana; et al. (Toxicology Letters, 2024)

Identifying pathways of pharmaceutical exposure in a mesoconsumer marine fish - N.A. Castillo; W.R. James; R.O. Santos; R. Rezek; D. Cerveny; R.E. Boucek; A.J. Adams; S. Trabelsi; A. Distrubell; M. Sandquist; J. Fick; T. Brodin; et al. (Journal of Hazardous Materials, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Epidemiological insights into neonatal deaths: The role of cooking fuel pollution in Colombia - Federico Andrade-Rivas; Arnold Ikedichi Okpani; Diego I. Lucumí; Maria D. Castillo; Mohammad Ehsanul Karim (International Journal of Hygiene and Environmental Health, 2024)

Straw digestibility in rice: Novel insights from pyrolysis GC-MS and biomass phenotyping - Mariana P. Silva; Caragh Whitehead; Reynante L. Ordonio; Trinidad C. Fernando; Mark Philip B. Castillo; Jeremias L. Ordonio; Tony Larson; Daniel J. Upton; Susan E. Hartley; Leonardo D. Gomez (Biomass and Bioenergy, 2024)

PHB production by Bacillus megaterium strain MNSH1-9K-1 using low-cost media - Andrea M. Rivas-Castillo; Alejandro Valdez-Calderón; Arturo F. Angeles-Padilla; César B. Figueroa-Ocampo; Sandra Carrillo-Ibarra; Maribel Quezada-Cruz; Arian Espinosa-Roa; Brandon D. Pérez-García; Norma G. Rojas-Avelizapa (Brazilian Journal of Microbiology, 2024)

Understanding pharmaceutical exposure and the potential for effects in marine biota: A survey of bonefish (Albula vulpes) across the Caribbean Basin - N.A. Castillo; W.R. James; R.O. Santos; R. Rezek; D. Cerveny; R.E. Boucek; A.J. Adams; T. Goldberg; L. Campbell; A.U. Perez; J.J. Schmitter-Soto; J.P. Lewis; et al. (Chemosphere, 2024)

Incorporating high-resolution climate, remote sensing and topographic data to map annual forest growth in central and eastern Europe - Jernej Jevšenak; Marcin Klisz; Jiří Mašek; Vojtěch Čada; Pavel Janda; Miroslav Svoboda; Ondřej Vostarek; Vaclav Treml; Ernst van der Maaten; Andrei Popa; Ionel Popa; Marieke van der Maaten-Theunissen; et al. (Science of The Total Environment, 2024)

First insight into the natural biodegradation of cyanide in a gold tailings environment enriched in cyanide compounds - Megan D. Welman-Purchase; Julio Castillo; Alba Gomez-Arias; Andisiwe Matu; Robert N. Hansen (Science of The Total Environment, 2024)

Evaluating heavy metal levels and their toxicity risks in an urban lake in Chennai, India - D. Rosado; F. Castillo; I. Nambi; R. Sadhasivam; H. Valleru; N. Fohrer (International Journal of Environmental Science and Technology, 2024)
Many urban water bodies in Chennai, India receive untreated sewage that pollutes their waters. An example is the Sembakkam lake, in which water reaches the Pallikaranai marshland, a proposed Ramsar site. In 2019, the city experienced the worst water crisis in 30 years, and many lakes were extremely dry, favoring peaks of heavy metals. Therefore, this study focuses on analysing heavy metal pollution and evaluating its potential effects on biota. In situ parameters were measured and water, sediment, and water hyacinth samples were collected during four campaigns. Al, As, Cr, Cu, Fe, Mn, Ni, Pb, and Zn were measured in all samples. Digestions for total metal content were performed in solid samples and acetic acid extractions only in sediments. The average pH (7.89–8.46) was neutral-alkaline and electrical conductivities (1559–2864 µS/cm) were high. In water, Pb (average: 2.59 µg/l) posed the highest toxicity risk according to the United Nations Economic Commission for Europe, followed by Cu and Cr. In sediment, Cu and Cr reached severe enrichment with respect to continental crust (averages: 19.46 and 13.65) followed by Ni and Zn with moderately severe enrichment. Ni produced the highest toxicity risk (average: 76.18 mg/kg), above the effects range-median, followed by Cr and Cu, between the effects range-low and effects range-median. The highest bioaccumulation factors in the water hyacinth were in the roots. Translocation factors showed similar concentrations in stems and leaves. Proper management of sewage is necessary to diminish the potential deleterious effects of metals on aquatic life and by extension, human health.

Human health risk assessment due to mercury use in gold mining areas in the Ecuadorian Andean region - Carlos Mestanza-Ramón; Samantha Jiménez-Oyola; Alex Vinicio Gavilanes Montoya; Danny Daniel Castillo Vizuete; Giovanni D'Orio; Juan Cedeño-Laje; Doménica Urdánigo; Salvatore Straface (Chemosphere, 2023)

Tracking the permeation of PVS2 components in living Mentha x Piperita SHOOT TIPS USING OPTICAL MICROSCOPIES - Heidi D. Kreckel; Albert Ochoa Castillo; Remi Bonnart; Gayle M. Volk; Dominik Stich; Nancy E. Levinger (Cryobiology, 2023)

Decoupling of short-lived radiogenic and helium isotopes in the Marquesas hotspot - M.-T. Herret; B.J. Peters; D. Kim; P.R. Castillo; A. Mundl-Petermeier (Chemical Geology, 2023)

Dirofilaria immitis in pet dogs from the metropolitan area of the Colombian Caribbean - Maria A. Badillo-Viloria; Ignacio García-Bocanegra; Rodrigo J. de Lavalle-Galvis; Remigio Martínez; Steffania de la Rosa-Jaramillo; Adriana Castillo-Castañeda; Juan D. Ramírez; David Cano-Terriza (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

In vitro macronutrient digestibility and mineral bioaccessibility of lentil-based pasta: The influence of cellular intactness - D. Duijsens; A.I. Alfie Castillo; S.H.E. Verkempinck; K. Pälchen; M.E. Hendrickx; T. Grauwet (Food Chemistry, 2023)

Assessment of Hg pollution in stream waters and human health risk in areas impacted by mining activities in the Ecuadorian Amazon - Carlos Mestanza-Ramón; Samantha Jiménez-Oyola; Alex Vinicio Gavilanes Montoya; Danny Daniel Castillo Vizuete; Giovanni D’Orio; Juan Cedeño-Laje; Salvatore Straface (Environmental Geochemistry and Health, 2023)
Illegal gold mining activities have contributed to the release and mobilization of Hg and environmental degradation in many parts of the world. This study aims to determine the concentration of Hg in five provinces of the Amazon Region of Ecuador, in addition to assessing the risk to human health of exposed populations, applying deterministic and probabilistic methods. For this purpose, 147 water samples were collected in rivers and streams crossing and/or located near mining areas. As a result, 100% of the samples analyzed exceeded the maximum permissible limit (MPL) according to the water quality criteria for the preservation of aquatic life of the Ecuadorian regulations, while 7% of the samples exceeded the MPL for drinking water. On the other hand, considering the European Environmental Quality Standard (EQS) for surface water bodies, in our study, 100% of the samples exceed the maximum permissible limit (0.07 µg/L), and with respect to the Canadian water quality guidelines, 35% of the samples exceed the permissible limit (0.001 mg/l) for drinking water, and 100% of the samples exceed the limit for life in water bodies (0.0001 mg/l). The risk assessment revealed that the probability of developing adverse health effects from exposure to Hg is below the recommended limits according to the probabilistic assessment; this is in relation to the criterion of residential and recreational use of water resources. However, it was identified that the child population doubles the acceptable systemic risk level according to the results of the deterministic assessment in the residential scenario. This information can be used by decision-makers to implement strategies to reduce Hg contamination and exposure of the population in Ecuadorian Amazonian rivers.

Ecological aspects of false killer whales ( Pseudorca crassidens ) from Mexican Pacific and Southern California waters - Camila Lazcano‐Pacheco; Acilegna J. Castillo‐Sánchez; Christian D. Ortega‐Ortiz; Ibiza Martínez‐Serrano; Francisco Villegas‐Zurita; Astrid Frisch‐Jordán; Oscar R. Guzón‐Zatarain; Katherina Audley; Nicola Ransome; Jaime Bolaños‐Jiménez; Jorge Urbán‐R.; Annie B. Douglas (Marine Mammal Science, 2023)

First afrosoricid out of Africa: an example of Pliocene ‘tourism’ in Europe - Vicente D. Crespo; Penélope Cruzado-Caballero; Carolina Castillo (Palaeoworld, 2023)

Frequent defoliation of perennial legume-grass bicultures alters soil carbon dynamics - Cristhian dos Santos Teixeira; Buck T. Castillo; Lukas Bernhardt; Nicholas D. Warren; Claudia Petry; Jessica G. Ernakovich; Richard G. Smith; Serita D. Frey (Plant and Soil, 2023)

Gill microbiomes accurately predict the geographic origin of bonefish (Albula vulpes) when combined with machine learning models - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Shimana M. Bose; Addiel U. Perez; Juan J. Schmitter-Soto; Sahar Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Understanding the landscape evolution of El Mogote barrier spit, Baja California Sur, Mexico, using OSL dating, satellite images and a multivariate analysis - A. Valoix; E. Muñoz-Salinas; M. Castillo; D. Sanderson; A. Cresswell (Journal of South American Earth Sciences, 2023)

Spatio‐temporal patterns of ichthyoplankton in southern Chilean Patagonia: β‐diversity and associated environmental factors - Mauricio F. Landaeta; Lissette D. Paredes; Manuel I. Castillo; M. Teresa González (Fisheries Oceanography, 2023)
Fjords play an important role in biological productivity worldwide but are vulnerable to climate/anthropogenic effects. Chilean Patagonia (41°S–55°S) is one of the largest fjord ecosystems in the world, characterized by a complex geography with highly heterogeneous hydrographic conditions and a permanent input from oceanic water mass, both of which influence the ichthyoplankton distributional patterns. In this study, we analysed the distributional patterns of ichthyoplankton and its diversity during austral spring from 1996, 2009 and 2019 in the southern Chilean fjords (47°S–54°S). The area shows important latitudinal gradients of sea surface temperature (from 15°C to 5°C), fjord‐ocean variability in salinity (from 23 to 33) and water column temperature (3°C to 9°C). Spatial (but not temporal) variations in the composition and abundance of ichthyoplankton were recorded, caused mainly by differences in the abundance of larval Sprattus fuegensis , Maurolicus australis and Sebastes oculatus . Richness was higher on continental shelf and the lowest nearby fjord's head and ice fields. At the spatial scale, β‐diversity showed an increased species replacement (turnover) across areas, suggesting an important role of environmental conditions (e.g., salinity and water stratification) on the larval fish structure in this region. Ordination analysis indicates that changes in salinity and temperature, caused by ice melting, is the main environmental factor influencing the abundance of larval Thysanopsetta naresi (1996), Cataetyx messieri (2009) and Bathylagichthys parini (2019). Finally, this study highlights the importance of the conservation and protection of the Chilean Patagonia and monitoring ichthyoplankton communities, which are vital biomarkers of ecosystem health.

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

The dynamics of arsenic and copper in solid and aqueous phases in reactive confluences receiving acid drainage: The role of turbidity and particle size - J.A. Díaz; D. Castillo; R. Oyarzún; A. Briso; M. Montecinos; P. Pastén (Environmental Pollution, 2023)

Forest buffer-strips mitigate the negative impact of oil palm plantations on stream communities - O.A. Rojas-Castillo; S. Kepfer-Rojas; N. Vargas; D. Jacobsen (Science of The Total Environment, 2023)

Associations between early introduction to complementary foods, subsequent cereal-added bottle feeding and daily macronutrient intake among infants - Jigna M. Dharod; Marlen Hernandez; Jeffrey D. Labban; Maureen M. Black; Alice Ammerman; Christina Frazier; Nichole Raynor; Isa Ramos-Castillo (Appetite, 2023)

Community Patterns and Environmental Associations for the Early Life Stages of Fishes in a Highly Transformed Estuary - Gonzalo C. Castillo; Trishelle Tempel; Steven B. Slater; Brian Mahardja; Morgan D. Gilbert (Estuaries and Coasts, 2023)
Estuaries are important fish nursery areas, yet little is known of how environmental forcing influences estuarine fishes during their early life stages. We analyzed environmental and larval-juvenile fish community data in the upper San Francisco Estuary (SFE) from spring to early summer 1995–2017, to better understand drivers of spatiotemporal community patterns in this highly modified estuary. We evaluated community patterns based on the relative abundance and diversity of native and introduced fish in the SFE and their predominant distribution (pelagic, demersal). The upper SFE experienced a downward trend of freshwater outflow and upward trends of temperature and salinity intrusion. Fish relative abundance only showed long-term downtrends for native and introduced pelagic fish groups. The most influential habitat components for relative abundance and diversity of fish groups were in decreasing order: temperature, salinity, Secchi depth, bottom depth, and zooplankton biomass. Early life stages of native and introduced fishes were generally segregated spatially and temporally, with native fishes more associated with cooler, saltier, and higher turbidity habitats during early to mid-spring compared to introduced fishes during late spring to early summer. Community ordination showed that environmental (temperature, salinity, outflow, Secchi depth, and zooplankton biomass) and spatiotemporal factors (month and depth), explained nearly 40% of the total variance. Our results suggest that the shorter duration of planktonic and nektonic stages of demersal fish groups results in higher resiliency compared to pelagic fishes. The declining abundance of pelagic fishes overall seems to be linked to drought effects and human-induced synergistic interactions intensified by climate change.

Surface wind strength and sea surface temperature connections along the south peruvian coast during the last 150 years - F. Briceño-Zuluaga; V. Flores-Aqueveque; J. Nogueira; A. Castillo; J. Cardich; J. Rutllant; S. Caquineau; A. Sifeddine; R. Salvatteci; J. Valdes; D. Gutierrez (Aeolian Research, 2023)

Aerosolized aqueous dust extracts collected near a drying lake trigger acute neutrophilic pulmonary inflammation reminiscent of microbial innate immune ligands - Trevor A. Biddle; Keziyah Yisrael; Ryan Drover; Qi Li; Mia R. Maltz; Talyssa M. Topacio; Jasmine Yu; Diana Del Castillo; Daniel Gonzales; Hannah L. Freund; Mark P. Swenson; Malia L. Shapiro; et al. (Science of The Total Environment, 2023)

Water-rich C-type asteroids as early solar system carbonate factories - Victoria Froh; Maitrayee Bose; Martin D. Suttle; Jacopo Nava; Luigi Folco; Lynda B. Williams; Julie Castillo-Rogez (Icarus, 2023)

Correction to: Viruses of Atlantic Bonefsh (Albula vulpes) in Florida and the Caribbean show geographic patterns consistent with population declines - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Addiel Perez; Juan J. Schmitter-Soto; Sahar C. Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Viruses of Atlantic Bonefish (Albula vulpes) in Florida and the Caribbean show geographic patterns consistent with population declines - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Addiel Perez; Juan J. Schmitter-Soto; Sahar C. Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

A review of estimation methods for natural mortality and their performance in the context of fishery stock assessment - Mark N. Maunder; Owen S. Hamel; Hui-Hua Lee; Kevin R. Piner; Jason M. Cope; André E. Punt; James N. Ianelli; Claudio Castillo-Jordán; Maia S. Kapur; Richard D. Methot (Fisheries Research, 2023)

Lupeol acetate isolated from Chrysophyllum cainito L. fruit as a template for the synthesis of N -alkyl-arylsulfonamide derivatives and their synergistic effects with metronidazole against Trichomonas vaginalis - Angel D. Herrera-España; Julio A. Aguiar-Pech; M. Elizbeth Alvarez-Sánchez; Victor E. Arana-Argáez; Cynthia K. Palomar-Gómez; Armin G. Jiménez-Ross; David Cáceres-Castillo; Rubén M. Carballo; Julio C. Torres-Romero (Natural Product Research, 2022)

A novel series of pyrazole derivatives toward biological applications: experimental and conceptual DFT characterization - Pedro D. Ortiz; Judith Castillo-Rodriguez; Jorge Tapia; Ximena Zarate; Gabriel A. Vallejos; Vanesa Roa; Elies Molins; Carlos Bustos; Eduardo Schott (Molecular Diversity, 2022)

Metaomics unveils the contribution of Alteromonas bacteria to carbon cycling in marine oxygen minimum zones - Carlos Henríquez-Castillo; Alvaro M. Plominsky; Salvador Ramírez-Flandes; Anthony D. Bertagnolli; Frank J. Stewart; Osvaldo Ulloa (Frontiers in Marine Science, 2022)
Gammaproteobacteria of the genus Alteromonas are prominent members of pelagic marine microbial communities, playing critical roles in the aerobic degradation of particulate organic matter. Comparative genomic studies of these microorganisms have mainly focused on the metabolic and genomic plasticity of strains isolated primarily from oxygenated environments. In this study, we show that Alteromonas significantly contribute to marine microbial communities from suboxic waters ([O 2 ] < 5 uM) in both the free-living (FL) and particle-attached (PA) fractions, but considerably decrease in abundance in the anoxic waters. The highest proportion of Alteromonas transcripts was found within the secondary fluorescence maximum (SFM) of Oxygen Minimum Zones (OMZs). This metatranscriptomic information suggests an in situ coupling of Alteromonas iron (Fe) and carbon metabolisms, and a relevant role of the glyoxylate cycle across the different layers of the OMZs. This study demonstrates that Alteromonas is an abundant and active member of the OMZ microbial communities, with a potentially significant impact on the carbon cycling in these ecosystems. These results provide valuable environmental evidence to support previous culture-based studies assessing the physiology and ecology of these ubiquitous marine heterotrophs under low-oxygen conditions.

Cytotoxic and antiproliferative activity of thiazole derivatives of Ochraceolide A - Angel D. Herrera-España; Jenner Us-Martín; Carlos Quintal-Novelo; Gumersindo Mirón-López; Ramiro F. Quijano-Quiñones; David Cáceres-Castillo; Manlio Graniel-Sabido; Rosa E. Moo-Puc; Gonzalo J. Mena-Rejón (Natural Product Research, 2022)

Physicochemical Control of Caribbean Coral Calcification Linked to Host and Symbiont Responses to Varying pCO2 and Temperature - Robert A. Eagle; Maxence Guillermic; Illian De Corte; Blanca Alvarez Caraveo; Colleen B. Bove; Sambuddha Misra; Louise P. Cameron; Karl D. Castillo; Justin B. Ries (Journal of Marine Science and Engineering, 2022)
It is thought that the active physiological regulation of the chemistry of a parent fluid is an important process in the biomineralization of scleractinian corals. Biological regulation of calcification fluid pH (pHCF) and other carbonate chemistry parameters ([CO32−]CF, DICCF, and ΩCF) may be challenged by CO2 driven acidification and temperature. Here, we examine the combined influence of changing temperature and CO2 on calcifying fluid regulation in four common Caribbean coral species—Porites astreoides, Pseudodiploria strigosa, Undaria tenuifolia, and Siderastrea siderea. We utilize skeletal boron geochemistry (B/Ca and δ11B) to probe the pHCF, [CO32−]CF, and DICCF regulation in these corals, and δ13C to track changes in the sources of carbon for calcification. Temperature was found to not influence pHCF regulation across all pCO2 treatments in these corals, in contrast to recent studies on Indo-Pacific pocilloporid corals. We find that [DIC]CF is significantly lower at higher temperatures in all the corals, and that the higher temperature was associated with depletion of host energy reserves, suggesting [DIC]CF reductions may result from reduced input of respired CO2 to the DIC pool for calcification. In addition, δ13C data suggest that under high temperature and CO2 conditions, algal symbiont photosynthesis continues to influence the calcification pool and is associated with low [DIC]CF in P. strigosa and P. astreoides. In P. astreoides this effect is also associated with an increase in chlorophyll a concentration in coral tissues at higher temperatures. These observations collectively support the assertion that physicochemical control over coral calcifying fluid chemistry is coupled to host and symbiont physiological responses to environmental change, and reveals interspecific differences in the extent and nature of this coupling.

Alpinumisoflavone against cancer pro-angiogenic targets: In silico, In vitro, and In ovo evaluation - Honeymae C. Alos; Junie B. Billones; Agnes L. Castillo; Ross D. Vasquez (DARU Journal of Pharmaceutical Sciences, 2022)

Stable inversion clines in a grasshopper species group despite complex geographical history - Noelia V. Guzmán; Petri Kemppainen; Daniela Monti; Elio R. D. Castillo; Marcela S. Rodriguero; Andrés F. Sánchez‐Restrepo; Maria Marta Cigliano; Viviana A. Confalonieri (Molecular Ecology, 2022)
Chromosomal inversions are known to play roles in adaptation and differentiation in many species. They involve clusters of correlated genes (i.e., loci in linkage disequilibrium, LD) possibly associated with environmental variables. The grasshopper “species complex” Trimerotropis pallidipennis comprises several genetic lineages distributed from North to South America in arid and semi‐arid high‐altitude environments. The southernmost lineage, Trimerotropis sp., segregates for four to seven putative inversions that display clinal variation, possibly through adaptation to temperate environments. We analysed chromosomal, mitochondrial and genome‐wide single nucleotide polymorphism data in 19 Trimerotropis sp. populations mainly distributed along two altitudinal gradients (MS and Ju). Populations across Argentina comprise two main chromosomally and genetically differentiated lineages: one distributed across the southernmost border of the “Andes Centrales,” adding evidence for a differentiation hotspot in this area; and the other widely distributed in Argentina. Within the latter, network analytical approaches to LD found three clusters of correlated loci (LD‐clusters), with inversion karyotypes explaining >79% of the genetic variation. Outlier loci associated with environmental variables mapped to two of these LD‐clusters. Furthermore, despite the complex geographical history indicated by population genetic analyses, the clines in inversion karyotypes have remained stable for more than 20 generations, implicating their role in adaptation and differentiation within this lineage. We hypothesize that these clines could be the consequence of a coupling between extrinsic postzygotic barriers and spatially varying selection along environmental gradients resulting in a hybrid zone. These results provide a framework for future investigations about candidate genes implicated in rapid adaptation to new environments.

NFĸB Targeting in Bone Marrow Mesenchymal Stem Cell-Mediated Support of Age-Linked Hematological Malignancies - Lauren S. Sherman; Shyam A. Patel; Marianne D. Castillo; Rachel Unkovic; Marcelo Taborga; Marina Gergues; Shaun Patterson; Jean-Pierre Etchegaray; Mohammed Jaloudi; Anupama Hooda-Nehra; Joshua Kra; Darling P. Rojas; et al. (Stem Cell Reviews and Reports, 2021)

Pharmacokinetic and pharmacodynamic properties of aerosolized (“vaped”) THC in adolescent male and female rats - C. M. Ruiz; A. Torrens; V. Lallai; E. Castillo; L. Manca; M. X. Martinez; D. N. Justeson; C. D. Fowler; D. Piomelli; S. V. Mahler (Psychopharmacology, 2021)

Use of pooled serum samples to assess herd disease status using commercially available ELISAs - Juan Heberth Hernandez-Medrano; Luis Fernando Espinosa-Castillo; Ana D. Rodriguez; Carlos G. Gutierrez; Wendela Wapenaar (Tropical Animal Health and Production, 2021)
Pooled samples are used in veterinary and human medicine as a cost-effective approach to monitor disease prevalence. Nonetheless, there is limited information on the effect of pooling on test performance, and research is required to determine the appropriate number of samples which can be pooled. Therefore, this study aimed to evaluate the use of pooled serum samples as a herd-level surveillance tool for infectious production-limiting diseases: bovine viral diarrhoea (BVD), infectious bovine rhinotracheitis (IBR), enzootic bovine leukosis (EBL) and Neospora caninum (NC), by investigating the maximum number of samples one can pool to identify one positive animal, using commercial antibody-detection ELISAs. Four positive field standards (PFS), one for each disease, were prepared by pooling highly positive herd-level samples diagnosed using commercially available ELISA tests. These PFS were used to simulate 18 pooled samples ranging from undiluted PFS to a dilution representing 1 positive in 1,000 animals using phosphate-buffered saline as diluent. A 1:10 dilution of the PFS resulted in positive results for IBR, BVD and EBL. Moreover, for IBR and BVD, results were still positive at 1:100 and 1:30 dilutions, respectively. However, for NC, a lower dilution (8:10) was required for a seropositive result. This study indicates that, at herd-level, the use of pooled serum is a useful strategy for monitoring infectious diseases (BVD, IBR and EBL) but not NC, using readily available diagnostic assays.

Probiotic Properties of Alcaligenes faecalis Isolated from Argyrosomus regius in Experimental Peritonitis (Rat Model) - A. I. Gutiérrez-Falcón; A. M. Ramos-Nuez; A. Espinosa de los Monteros y Zayas; D. F. Padilla Castillo; M. Isabel García-Laorden; F. J. Chamizo-López; F. Real Valcárcel; F. Artilles Campelo; A. Bordes Benítez; P. Nogueira Salgueiro; C. Domínguez Cabrera; J. C. Rivero-Vera; et al. (Probiotics and Antimicrobial Proteins, 2021)
A strain of Alcaligenes faecalis A12C ( A. faecalis A12C) isolated from Argyrosomus regius is a probiotic in fish. Previous experiments showed that A. faecalis A12C had inhibitory effects on the growth of multidrug-resistant bacteria. We aimed to confirm whether A. faecalis A12C is safe and has adequate intestinal colonization in experimental rats, and evaluate its efficacy in an animal model of peritonitis . We used 30 male rats, randomly divided into 6 groups ( n = 5): three groups (HA7, HA15, HA30) received A. faecalis A12C in drinking water (6 × 10 8 CFU/mL) for 7 days, and three control groups received drinking water only. All groups were evaluated at 7, 15, and 30 days. Survival after A. faecalis A12C administration was 100% in all groups. Mild eosinophilia (1.5%, p < 0.01) and increased aspartate aminotransferase (86 IU/L, p < 0.05) were observed in HA7, followed by progressive normalization. No histological signs of organ injury were found. We observed significant E. coli decline in faeces, parallel to an increase in A. faecalis A12C at 7 days. E. coli had a tendency to recover initial values, while A. faecalis A12C disappeared from the intestinal microbiota at 30 days. To evaluate its efficacy against peritonitis, we studied two additional groups of animals: IA group pretreated with A. faecalis A12C before E. coli intra-abdominal inoculation, and IC group inoculated with no A. faecalis A12C. We found an increase in C-reactive protein, alanine aminotransferase, urea, and eosinophils in IC animals when compared with IA. Peritonitis was more evident in IC than in IA animals. Our findings suggest that A. faecalis A12C altered clinically relevant parameters in sepsis and was associated with a lesser spread of infection.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Two offshore coral species show greater acclimatization capacity to environmental variation than nearshore counterparts in southern Belize - J. H. Baumann; C. B. Bove; L. Carne; I. Gutierrez; K. D. Castillo (Coral Reefs, 2021)

Exposure duration modulates the response of Caribbean corals to global change stressors - Hannah E. Aichelman; Colleen B. Bove; Karl D. Castillo; Jessica M. Boulton; Alyssa C. Knowlton; Olivia C. Nieves; Justin B. Ries; Sarah W. Davies (Limnology and Oceanography, 2021)
Global change, including rising temperatures and acidification, threatens corals globally. Although bleaching events reveal fine‐scale patterns of resilience, traits enabling persistence under global change remain elusive. We conducted a 95‐d controlled‐laboratory experiment investigating how duration of exposure to warming (~28, 31°C), acidification ( p CO 2 ~ 343 [present day], ~663 [end of century], ~3109 [extreme] μ atm), and their combination influences physiology of reef‐building corals ( Siderastrea siderea , Pseudodiploria strigosa ) from two reef zones on the Belize Mesoamerican Barrier Reef System. Every 30 d, net calcification rate, host protein and carbohydrate, chlorophyll a , and symbiont density were quantified for the same coral individual to characterize acclimation potential under global change. Coral physiologies of the two species were differentially affected by stressors and exposure duration was found to modulate these responses. Siderastrea siderea exhibited resistance to end of century p CO 2 and temperature stress, but calcification was negatively affected by extreme p CO 2 . However, S. siderea calcification rates remained positive after 95 d of extreme p CO 2 conditions, suggesting acclimation. In contrast, P. strigosa was more negatively influenced by elevated temperatures, which reduced most physiological parameters. An exception was nearshore P. strigosa , which maintained calcification rates under elevated temperature, suggesting local adaptation to the warmer environment of their natal reef zone. This work highlights how tracking coral physiology across various exposure durations can capture acclimatory responses to global change stressors.

The virus–host interface: Molecular interactions of Alphacoronavirus‐1 variants from wild and domestic hosts with mammalian aminopeptidase N - Ximena A. Olarte‐Castillo; Joana F. dos Remédios; Felix Heeger; Heribert Hofer; Stephan Karl; Alex D. Greenwood; Marion L. East (Molecular Ecology, 2021)
The Alphacoronavirus ‐ 1 species include viruses that infect numerous mammalian species. To better understand the wide host range of these viruses, better knowledge on the molecular determinants of virus–host cell entry mechanisms in wildlife hosts is essential. We investigated Alphacoronavirus ‐ 1 infection in carnivores using long‐term data on Serengeti spotted hyenas ( Crocuta crocuta ) and molecular analyses guided by the tertiary structure of the viral spike (S) attachment protein's interface with the host receptor aminopeptidase N (APN). We sequenced the complete 3′‐end region of the genome of nine variants from wild African carnivores, plus the APN gene of 15 wild carnivore species. Our results revealed two outbreaks of Alphacoronavirus ‐ 1 infection in spotted hyenas associated with genetically distinct canine coronavirus type II (CCoVII) variants. Within the receptor binding domain (RBD) of the S gene the residues that directly bind to the APN receptor were conserved in all variants studied, even those infecting phylogenetically diverse host taxa. We identified a variable region within RBD located next to a region that directly interacts with the APN receptor. Two residues within this variable region were under positive selection in hyena variants, indicating that both sites were associated with adaptation of CCoVII to spotted hyena APN. Analysis of APN sequences revealed that most residues that interact with the S protein are conserved in wild carnivores, whereas some adjacent residues are highly variable. Of the variable residues, four that are critical for virus–host binding were under positive selection and may modulate the efficiency of virus attachment to carnivore APN.

Seed bank dynamics of the annual halophyte Salicornia ramosissima: towards a sustainable exploitation of its wild populations - Alejandro Polo; Alba Fragoso; María D. Infante-Izquierdo; Francisco J. J. Nieva; Adolfo F. Muñoz-Rodríguez; Jesús M. Castillo (Plant Ecology, 2021)

Prior cortical activity differences during an action observation plus motor imagery task related to motor adaptation performance of a coordinated multi-limb complex task - J. Ignacio Serrano; Daniel Muñoz-García; Raúl Ferrer-Peña; Victor D’eudeville; Marta Brero; Maxime Boisson; M. Dolores del Castillo (Cognitive Neurodynamics, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Characterization of standardized heavy rainfall profiles for Barcelona city: clustering, rain amounts and intensity peaks - X. Lana; R. Rodríguez-Solà; M. D. Martínez; M. C. Casas-Castillo; C. Serra; A. Burgueño (Theoretical and Applied Climatology, 2020)

Eukaryotic plankton communities across reef environments in Bocas del Toro Archipelago, Panamá - Andrea M. Rodas; Rachel M. Wright; Logan K. Buie; Hannah E. Aichelman; Karl D. Castillo; Sarah W. Davies (Coral Reefs, 2020)

Size-Fractionated Contribution of Microbial Biomass to Suspended Organic Matter in the Eastern Tropical South Pacific Oxygen Minimum Zone - Sebastian I. Cantarero; Carlos Henríquez-Castillo; Nadia Dildar; Cristian A. Vargas; Peter von Dassow; Marcela Cornejo-D’Ottone; Julio Sepúlveda (Frontiers in Marine Science, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Patterns of environmental variability influence coral‐associated bacterial and algal communities on the Mesoamerican Barrier Reef - Lauren Speare; Sarah W. Davies; John P. Balmonte; Justin Baumann; Karl D. Castillo (Molecular Ecology, 2020)
A coral's capacity to alter its microbial symbionts may enhance its fitness in the face of climate change. Recent work predicts exposure to high environmental variability may increase coral resilience and adaptability to future climate conditions. However, how this heightened environmental variability impacts coral‐associated microbial communities remains largely unexplored. Here, we examined the bacterial and algal symbionts associated with two coral species of the genus Siderastrea with distinct life history strategies from three reef sites on the Belize Mesoamerican Barrier Reef System with low or high environmental variability. Our results reveal bacterial community structure, as well as alpha‐ and beta‐diversity patterns, vary by host species. Differences in bacterial communities between host species were partially explained by high abundance of Deltaproteobacteria and Rhodospirillales and high bacterial diversity in Siderastrea radians. Our findings also suggest Siderastrea spp. have dynamic core bacterial communities that likely drive differences observed in the entire bacterial community, which may play a critical role in rapid acclimatization to environmental change. Unlike the bacterial community, Symbiodiniaceae composition was only distinct between host species at high thermal variability sites, suggesting that different factors shape bacterial versus algal communities within the coral holobiont. Our findings shed light on how domain‐specific shifts in dynamic microbiomes may allow for unique methods of enhanced host fitness.

Heavy metals (lead, cadmium and zinc) from street dust in Monterrey, Mexico: ecological risk index - D. Castillo-Nava; M. Elias-Santos; U. J. López-Chuken; A. Valdés-González; L. G. de la Riva-Solís; M. P. Vargas-Pérez; L. J. Galán-Wong; H. A. Luna-Olvera (International Journal of Environmental Science and Technology, 2020)

A morphological, reproductive, and molt phenology database for 379 bird species from the Colombian Tropical Andes - Leydy J. Cardona‐Salazar; Yeny A. Benavides‐Ossa; Ángela M. Vargas‐Daza; Juan F. Betancurt‐Grisales; Mauricio Bohada‐Murillo; Estefani T. Martínez‐Sánchez; Marelid Cardona‐Romero; Ana Busi; William D. Tobón‐Escobar; Mateo Ortíz‐Giraldo; Daniela Gómez Castillo; Johnathan Alvarez‐Londoño; et al. (Ecology, 2020)
The Colombian Tropical Andes are one of the regions with highest bird diversity on Earth. However, information on bird morphology, reproductive phenology, and molt is particularly scarce in this region. Also, this region is heavily impacted by deforestation, and it is vulnerable to climate change. Hence, providing baseline information on life history and morphological traits will be essential to support future research on functional diversity, climate change effects, conservation, evolution, and phenology. To fill this gap, we have compiled information on bird distribution, morphology, molt, and reproductive phenology at 52 localities of the Department of Caldas, covering an elevation range between 148 and 3845 m. This compilation comprises a wide range of habitats, including native forests, forestry plantations, croplands, and paramo. Our database presents information for 3,398 records belonging to 379 bird species (representing 23 orders, 53 families, and 258 genera). From those records, 2,843 correspond to information collected in the field between 2008 and 2019, and the remaining 555 records correspond to specimens deposited in the Natural History Museum of the Caldas University, collected between 1969 and 2014. We measured nine morphological traits from all specimens: total culmen, gape, bill width, bill depth, tarsus, wing length, tail length, total length, and mass. We also have reproductive condition information for 257 species and molt information available for 378 species. The information contained in this data set represents ~20% of the Colombian avifauna and ~11% of the bird species richness in South America. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Fruit Set, Seed Viability and Germination of the European Native Spartina maritima in Southwest Iberian Peninsula - M. Dolores Infante-Izquierdo; Jesús M. Castillo; F. Javier J. Nieva; Ioana D. Rotundu; Francesca T. David; Brenda J. Grewell; Adolfo F. Muñoz-Rodríguez (Wetlands, 2020)

Meta-Analysis Reveals Reduced Coral Calcification Under Projected Ocean Warming but Not Under Acidification Across the Caribbean Sea - Colleen B. Bove; James Umbanhowar; Karl D. Castillo (Frontiers in Marine Science, 2020)

Lanthanum- and cerium-based functionalization of chars and activated carbons for the adsorption of fluoride and arsenic ions - E. E. Merodio-Morales; H. E. Reynel-Ávila; D. I. Mendoza-Castillo; C. J. Duran-Valle; A. Bonilla-Petriciolet (International Journal of Environmental Science and Technology, 2020)

Nearshore coral growth declining on the Mesoamerican Barrier Reef System - Justin H. Baumann; Justin B. Ries; John P. Rippe; Travis A. Courtney; Hannah E. Aichelman; Isaac Westfield; Karl D. Castillo (Global Change Biology, 2019)
Anthropogenic global change and local stressors are impacting coral growth and survival worldwide, altering the structure and function of coral reef ecosystems. Here, we show that skeletal extension rates of nearshore colonies of two abundant and widespread Caribbean corals ( Siderastrea siderea , Pseudodiploria strigosa ) declined across the Belize Mesoamerican Barrier Reef System (MBRS) over the past century, while offshore coral conspecifics exhibited relatively stable extension rates over the same temporal interval. This decline has caused nearshore coral extension rates to converge with those of their historically slower growing offshore coral counterparts. For both species, individual mass coral bleaching events were correlated with low rates of skeletal extension within specific reef environments, but no single bleaching event was correlated with low skeletal extension rates across all reef environments. We postulate that the decline in skeletal extension rates for nearshore corals is driven primarily by the combined effects of long‐term ocean warming and increasing exposure to higher levels of land‐based anthropogenic stressors, with acute thermally induced bleaching events playing a lesser role. If these declining trends in skeletal growth of nearshore S. siderea and P. strigosa continue into the future, the structure and function of these critical nearshore MBRS coral reef systems is likely to be severely impaired.

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Deep reef fishes in the world’s epicenter of marine biodiversity - Hudson T. Pinheiro; Bart Shepherd; Cristina Castillo; Rene A. Abesamis; Joshua M. Copus; Richard L. Pyle; Brian D. Greene; Richard R. Coleman; Robert K. Whitton; Emma Thillainath; Abner A. Bucol; Matthew Birt; et al. (Coral Reefs, 2019)

Recent emergence and extinction of the protection of telomeres 1c gene in Arabidopsis thaliana - Callie R. Kobayashi; Claudia Castillo-González; Yulia Survotseva; Elijah Canal; Andrew D. L. Nelson; Dorothy E. Shippen (Plant Cell Reports, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

The BeWo cell line derived from a human placental choriocarcinoma is permissive for respiratory syncytial virus infection - M. A. Velázquez-Cervantes; M. Martínez-Castillo; L. D. González-García; T. A. Vargas-Pavía; M. G. Martínez-Salazar; I. Mancilla-Herrera; G. León-Reyes; J. García-Cordero; A. C. Helguera-Repetto; M. León-Juárez (Virus Genes, 2019)

Gene flow, divergent selection and resistance to introgression in two species of morning glories ( Ipomoea ) - Joanna L. Rifkin; Allan S. Castillo; Irene T. Liao; Mark D. Rausher (Molecular Ecology, 2019)
Gene flow is thought to impede genetic divergence and speciation by homogenizing genomes. Recent theory and research suggest that sufficiently strong divergent selection can overpower gene flow, leading to loci that are highly differentiated compared to others. However, there are also alternative explanations for this pattern. Independent evidence that loci in highly differentiated regions are under divergent selection would allow these explanations to be distinguished, but such evidence is scarce. Here, we present multiple lines of evidence that many of the highly divergent SNP s in a pair of sister morning glory species, Ipomoea cordatotriloba and I. lacunosa , are the result of divergent selection in the face of gene flow. We analysed a SNP data set across the genome to assess the amount of gene flow, resistance to introgression and patterns of selection on loci resistant to introgression. We show that differentiation between the two species is much lower in sympatry than in allopatry, consistent with interspecific gene flow in sympatry. Gene flow appears to be substantially greater from I. lacunosa to I. cordatotriloba than in the reverse direction, resulting in sympatric and allopatric I. cordatotriloba being substantially more different than sympatric and allopatric I. lacunosa . Many SNP s highly differentiated in allopatry have experienced divergent selection, and, despite gene flow in sympatry, resist homogenization in sympatry. Finally, five out of eight floral and inflorescence characteristics measured exhibit asymmetric convergence in sympatry. Consistent with the pattern of gene flow, I. cordatotriloba traits become much more like those of I. lacunosa than the reverse. Our investigation reveals the complex interplay between selection and gene flow that can occur during the early stages of speciation.

Return period curves for extreme 5-min rainfall amounts at the Barcelona urban network - X. Lana; M. C. Casas-Castillo; C. Serra; R. Rodríguez-Solà; A. Redaño; A. Burgueño; M. D. Martínez (Theoretical and Applied Climatology, 2019)

Apparent timing of density banding in the Caribbean coral Siderastrea siderea suggests complex role of key physiological variables - B. E. Benson; J. P. Rippe; C. B. Bove; K. D. Castillo (Coral Reefs, 2019)

Corals sustain growth but not skeletal density across the Florida Keys Reef Tract despite ongoing warming - John P. Rippe; Justin H. Baumann; Daphne N. De Leener; Hannah E. Aichelman; Eric B. Friedlander; Sarah W. Davies; Karl D. Castillo (Global Change Biology, 2018)
Through the continuous growth of their carbonate skeletons, corals record information about past environmental conditions and their effect on colony fitness. Here, we characterize century‐scale growth records of inner and outer reef corals across ~200 km of the Florida Keys Reef Tract (FKRT) using skeletal cores extracted from two ubiquitous reef‐building species, Siderastrea siderea and Pseudodiploria strigosa . We find that corals across the FKRT have sustained extension and calcification rates over the past century but have experienced a long‐term reduction in skeletal density, regardless of reef zone. Notably, P. strigosa colonies exhibit temporary reef zone‐dependent reductions in extension rate corresponding to two known extreme temperature events in 1969–1970 and 1997–1998. We propose that the subtropical climate of the FKRT may buffer corals from chronic growth declines associated with climate warming, though the significant reduction in skeletal density may indicate underlying vulnerability to present and future trends in ocean acidification.

Feeding ecology of invasive lionfish (Pterois volitans and Pterois miles) in the temperate and tropical western Atlantic - Jonathan Peake; Alex K. Bogdanoff; Craig A. Layman; Bernard Castillo; Kynoch Reale-Munroe; Jennifer Chapman; Kristen Dahl; William F. Patterson III; Corey Eddy; Robert D. Ellis; Meaghan Faletti; Nicholas Higgs; et al. (Biological Invasions, 2018)

Dynamic fuzzy neural network for simulating the fixed-bed adsorption of cadmium, nickel, and zinc on bone char - F. A. Gordillo-Ruíz; F. J. Sánchez-Ruíz; D. I. Mendoza-Castillo; H. E. Reynel-Ávila; A. Bonilla-Petriciolet (International Journal of Environmental Science and Technology, 2018)

Symbiodinium Functional Diversity in the Coral Siderastrea siderea Is Influenced by Thermal Stress and Reef Environment, but Not Ocean Acidification - Sarah W. Davies; Justin B. Ries; Adrian Marchetti; Karl D. Castillo (Frontiers in Marine Science, 2018)

Threats to intact tropical peatlands and opportunities for their conservation - K.H. Roucoux; I.T. Lawson; T.R. Baker; D. Del Castillo Torres; F.C. Draper; O. Lähteenoja; M.P. Gilmore; E.N. Honorio Coronado; T.J. Kelly; E.T.A. Mitchard; C.F. Vriesendorp (Conservation Biology, 2017)
Large, intact areas of tropical peatland are highly threatened at a global scale by the expansion of commercial agriculture and other forms of economic development. Conserving peatlands on a landscape scale, with their hydrology intact, is of international conservation importance to preserve their distinctive biodiversity and ecosystem services and maintain their resilience to future environmental change. We explored threats to and opportunities for conserving remaining intact tropical peatlands; thus, we excluded peatlands of Indonesia and Malaysia, where extensive deforestation, drainage, and conversion to plantations means conservation in this region can protect only small fragments of the original ecosystem. We focused on a case study, the Pastaza‐Marañón Foreland Basin (PMFB) in Peru, which is among the largest known intact tropical peatland landscapes in the world and is representative of peatland vulnerability. Maintenance of the hydrological conditions critical for carbon storage and ecosystem function of peatlands is, in the PMFB, primarily threatened by expansion of commercial agriculture linked to new transport infrastructure that is facilitating access to remote areas. There remain opportunities in the PMFB and elsewhere to develop alternative, more sustainable land‐use practices. Although some of the peatlands in the PMFB fall within existing legally protected areas, this protection does not include the most carbon‐dense (domed pole forest) areas. New carbon‐based conservation instruments (e.g., REDD+, Green Climate Fund), developing markets for sustainable peatland products, transferring land title to local communities, and expanding protected areas offer pathways to increased protection for intact tropical peatlands in Amazonia and elsewhere, such as those in New Guinea and Central Africa which remain, for the moment, broadly beyond the frontier of commercial development.

Short-term and long-term effects of diazepam on the memory for discrimination and generalization of scopolamine - C. Casasola-Castro; L. Weissmann-Sánchez; E. Calixto-González; A. Aguayo-Del Castillo; D. N. Velázquez-Martínez (Psychopharmacology, 2017)

Impact of severe hematological abnormalities in the outcome of hospitalized patients with influenza virus infection - A. Lalueza; H. Trujillo; J. Laureiro; B. Ayuso; P. Hernández-Jiménez; C. Castillo; M. Torres; D. Folgueira; O. Madrid; C. Díaz-Pedroche; E. Arrieta; C. Arévalo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Comparative assessment of Vibrio virulence in marine fish larvae - A Rønneseth; D Castillo; P D'Alvise; Ø Tønnesen; G Haugland; T Grotkjær; K Engell‐Sørensen; L Nørremark; Ø Bergh; H I Wergeland; L Gram (Journal of Fish Diseases, 2017)
Vibrionaceae infections are a major obstacle for marine larviculture; however, little is known about virulence differences of Vibrio strains. The virulence of Vibrio strains, mostly isolated from vibriosis outbreaks in farmed fish, was tested in larval challenge trials with cod ( Gadus morhua ), turbot ( Scophthalmus maximus ) and halibut ( Hippoglossus hippoglossus ) using a multiwell dish assays with single‐egg/larvae cultures. The strains differed significantly in virulence as some caused a high mortality of larva reaching 100% mortality after a few days, while others had no or only marginal effects on survival. Some Vibrio strains were pathogenic in all of the larva species, while some caused disease only in one of the species. Twenty‐nine of the Vibrio anguillarum strains increased the mortality of larvae from at least one fish species; however, pathogenicity of the strains differed markedly. Other Vibrio species had no or less pronounced effects on larval mortalities. Iron uptake has been related to V. anguillarum virulence; however, the presence or absence of the plasmid pJM 1 encoding anguibactin did not correlate with virulence. The genomes of V. anguillarum were compared (D. Castillo, P.W. D'Alvise, M. Middelboe & L. Gram, unpublished data) and most of the high‐virulent strains had acquired virulence genes from other pathogenic Vibrio .

Native‐predator–invasive‐prey trophic interactions in Tierra del Fuego: the beginning of biological resistance? - Simón P. Castillo; Ramiro D. Crego; Jaime E. Jiménez; Ricardo Rozzi (Ecology, 2017)

Hexavalent chromium bioreduction and chemical precipitation of sulphate as a treatment of site-specific fly ash leachates - Errol D. Cason; Peter J. Williams; Elizabeth Ojo; Julio Castillo; Mary F. DeFlaun; Esta van Heerden (World Journal of Microbiology and Biotechnology, 2017)

A Review of Protist Grazing Below the Photic Zone Emphasizing Studies of Oxygen-Depleted Water Columns and Recent Applications of In situ Approaches - Luis E. Medina; Craig D. Taylor; Maria G. Pachiadaki; Carlos Henríquez-Castillo; Osvaldo Ulloa; Virginia P. Edgcomb (Frontiers in Marine Science, 2017)

Canine distemper virus in the Serengeti ecosystem: molecular adaptation to different carnivore species - Veljko M. Nikolin; Ximena A. Olarte‐Castillo; Nikolaus Osterrieder; Heribert Hofer; Edward Dubovi; Camila J. Mazzoni; Edgar Brunner; Katja V. Goller; Robert D. Fyumagwa; Patricia D. Moehlman; Dagmar Thierer; Marion L. East (Molecular Ecology, 2017)
Was the 1993/1994 fatal canine distemper virus ( CDV ) epidemic in lions and spotted hyaenas in the Serengeti ecosystem caused by the recent spillover of a virulent domestic dog strain or one well adapted to these noncanids? We examine this question using sequence data from 13 ‘Serengeti’ strains including five complete genomes obtained between 1993 and 2011. Phylogenetic and haplotype network analyses reveal that strains from noncanids during the epidemic were more closely related to each other than to those from domestic or wild canids. All noncanid ‘Serengeti’ strains during the epidemic encoded: (1) one novel substitution G134S in the CDV ‐V protein; and (2) the rare amino acid combination 519I/549H at two sites under positive selection in the region of the CDV ‐H protein that binds to SLAM ( CD 150) host cell receptors. Worldwide, only a few noncanid strains in the America II lineage encode CDV ‐H 519I/549H. All canid ‘Serengeti’ strains during the epidemic coded CDV ‐V 134G, and CDV ‐H 519R/549Y, or 519R/549H. A functional assay of cell entry revealed the highest performance by CDV ‐H proteins encoding 519I/549H in cells expressing lion SLAM receptors, and the highest performance by proteins encoding 519R/549Y, typical of dog strains worldwide, in cells expressing dog SLAM receptors. Our findings are consistent with an epidemic in lions and hyaenas caused by CDV variants better adapted to noncanids than canids, but not with the recent spillover of a dog strain. Our study reveals a greater complexity of CDV molecular epidemiology in multihost environments than previously thought.

Tamoxifen dosing for Cre-mediated recombination in experimental bronchopulmonary dysplasia - Jordi Ruiz-Camp; José Alberto Rodríguez-Castillo; Susanne Herold; Konstantin Mayer; István Vadász; Michelle D. Tallquist; Werner Seeger; Katrin Ahlbrecht; Rory E. Morty (Transgenic Research, 2017)

Variability among strains of Aspergillus section Nigri with capacity to degrade tannic acid isolated from extreme environments - F. Lara-Victoriano; F. Veana; F. D. Hernández-Castillo; C. N. Aguilar; M. H. Reyes-Valdés; R. Rodríguez-Herrera (Archives of Microbiology, 2017)

Thermal and pCO2 Stress Elicit Divergent Transcriptomic Responses in a Resilient Coral - Sarah W. Davies; Adrian Marchetti; Justin B. Ries; Karl D. Castillo (Frontiers in Marine Science, 2016)

Implementation of an experimental nutrient film technique-type aquaponic system - D. Castillo-Castellanos; I. Zavala-Leal; J. M. J. Ruiz-Velazco; A. Radilla-García; J. T. Nieto-Navarro; C. A. Romero-Bañuelos; J. González-Hernández (Aquaculture International, 2016)

Utilizing an Ingestible Biosensor to Assess Real-Time Medication Adherence - Peter R. Chai; Jose Castillo-Mancilla; Eric Buffkin; Chad Darling; Rochelle K. Rosen; Keith J. Horvath; Edwin D. Boudreaux; Gregory K. Robbins; Patricia L. Hibberd; Edward W. Boyer (Journal of Medical Toxicology, 2015)

Predictive classification of self-paced upper-limb analytical movements with EEG - Jaime Ibáñez; J. I. Serrano; M. D. del Castillo; J. Minguez; J. L. Pons (Medical & Biological Engineering & Computing, 2015)

Genetics of systemic sclerosis - Lara Bossini-Castillo; Elena López-Isac; Maureen D. Mayes; Javier Martín (Seminars in Immunopathology, 2015)

Chemical modification of Byrsonima crassifolia with citric acid for the competitive sorption of heavy metals from water - J. Monroy-Figueroa; D. I. Mendoza-Castillo; A. Bonilla-Petriciolet; M. A. Pérez-Cruz (International Journal of Environmental Science and Technology, 2015)

Effects of cytomegalovirus infection in human neural precursor cells depend on their differentiation state - H. M. González-Sánchez; A. Monsiváis-Urenda; C. A. Salazar-Aldrete; A. Hernández-Salinas; D. E. Noyola; M. E. Jiménez-Capdeville; A. Martínez-Serrano; C. G. Castillo (Journal of NeuroVirology, 2015)

Assessment of the risk of failure of high voltage substations due to environmental conditions and pollution on insulators - Rafael Castillo Sierra; Oscar Oviedo-Trespalacios; John E. Candelo; Jose D. Soto (Environmental Science and Pollution Research, 2015)

Removal of heavy metals and arsenic from aqueous solution using textile wastes from denim industry - D. I. Mendoza-Castillo; C. K. Rojas-Mayorga; I. P. García-Martínez; M. A. Pérez-Cruz; V. Hernández-Montoya; A. Bonilla-Petriciolet; M. A. Montes-Morán (International Journal of Environmental Science and Technology, 2015)

World Squid Fisheries - Alexander I. Arkhipkin; Paul G. K. Rodhouse; Graham J. Pierce; Warwick Sauer; Mitsuo Sakai; Louise Allcock; Juan Arguelles; John R. Bower; Gladis Castillo; Luca Ceriola; Chih-Shin Chen; Xinjun Chen; et al. (Reviews in Fisheries Science & Aquaculture, 2015)

The influence of atmospheric conditions on the leakage current of ceramic insulators on the Colombian Caribbean coast - Rafael Castillo Sierra; Oscar Oviedo-Trespalacios; John E. Candelo; Jose D. Soto (Environmental Science and Pollution Research, 2015)

Invasive Populations of Elephantgrass Differ in Morphological and Growth Characteristics from Clones Selected for Biomass Production - Lynn E. Sollenberger; Kenneth R. Woodard; João M. B. Vendramini; John E. Erickson; Kenneth A. Langeland; M. Kimberly Mullenix; Chaein Na; Miguel S. Castillo; Maria Gallo; Christine D. Chase; Yolanda López (BioEnergy Research, 2014)

Development of plaque assay for Chilean Infectious Salmon Anaemia Virus, application for virus purification and titration in salmon ASK cells - M T Castillo‐Cerda; L Cottet; D Toro‐Ascuy; E Spencer; M Cortez‐San Martín (Journal of Fish Diseases, 2014)

Critical slowing down and noise-induced intermittency in bistable perception: bifurcation analysis - Alexander N. Pisarchik; Rider Jaimes-Reátegui; C. D. Alejandro Magallón-García; C. Obed Castillo-Morales (Biological Cybernetics, 2014)

Begomovirus diversity in tomato crops and weeds in Ecuador and the detection of a recombinant isolate of rhynchosia golden mosaic Yucatan virus infecting tomato - Lenin C. Paz-Carrasco; Gloria P. Castillo-Urquiza; Alison T. M. Lima; Cesar A. D. Xavier; Leticia M. Vivas-Vivas; Eduardo S. G. Mizubuti; F. Murilo Zerbini (Archives of Virology, 2014)

Conservation strategies for coastal wetlands in the Gulf of California, Mexico - Hem Nalini Morzaria-Luna; Alejandro Castillo-López; Gustavo D. Danemann; Peggy Turk-Boyer (Wetlands Ecology and Management, 2014)

Partial characterisation of digestive proteases of the Mayan cichlid Cichlasoma urophthalmus - C. A. Cuenca-Soria; C. A. Álvarez-González; J. L. Ortiz-Galindo; H. Nolasco-Soria; D. Tovar-Ramírez; R. Guerrero-Zárate; A. Castillo-Domínguez; M. A. Perera-García; R. Hernández-Gómez; E. Gisbert (Fish Physiology and Biochemistry, 2014)

Prospecting metal-resistant plant-growth promoting rhizobacteria for rhizoremediation of metal contaminated estuaries using Spartina densiflora - L. Andrades-Moreno; I. del Castillo; R. Parra; B. Doukkali; S. Redondo-Gómez; P. Pérez-Palacios; M. A. Caviedes; E. Pajuelo; I. D. Rodríguez-Llorente (Environmental Science and Pollution Research, 2014)

Multiple domestications of the Mesoamerican gene pool of lima bean (Phaseolus lunatus L.): evidence from chloroplast DNA sequences - R. H. Andueza-Noh; M. L. Serrano-Serrano; M. I. Chacón Sánchez; I. Sanchéz del Pino; L. Camacho-Pérez; J. Coello-Coello; J. Mijangos Cortes; D. G. Debouck; J. Martínez-Castillo (Genetic Resources and Crop Evolution, 2013)

The Mexican Sugarcane Industry: Overview, Constraints, Current Status and Long-Term Trends - N. Aguilar-Rivera; D. A. Rodríguez L.; V. Enríquez R.; A. Castillo M.; A. Herrera S. (Sugar Tech, 2012)

Muscular strength and markers of insulin resistance in European adolescents: the HELENA Study - D. Jiménez-Pavón; F. B. Ortega; J. Valtueña; J. Castro-Piñero; S. Gómez-Martínez; M. Zaccaria; F. Gottrand; D. Molnár; M. Sjöström; M. González-Gross; M. J. Castillo; L. A. Moreno; et al. (European Journal of Applied Physiology, 2012)

Diversity of Flavobacterium psychrophilum and the potential use of its phages for protection against bacterial cold water disease in salmonids - D Castillo; G Higuera; M Villa; M Middelboe; I Dalsgaard; L Madsen; R T Espejo (Journal of Fish Diseases, 2012)
Flavobacterium psychrophilum causes rainbow trout fry syndrome (RTFS) and cold water disease (CWD) in salmonid aquaculture. We report characterization of F. psychrophilum strains and their bacteriophages isolated in Chilean salmonid aquaculture. Results suggest that under laboratory conditions phages can decrease mortality of salmonids from infection by their F. psychrophilum host strain. Twelve F. psychrophilum isolates were characterized, with DNA restriction patterns showing low diversity between strains despite their being obtained from different salmonid production sites and from different tissues. We isolated 15 bacteriophages able to infect some of the F. psychrophilum isolates and characterized six of them in detail. DNA genome sizes were close to 50 Kbp and corresponded to the Siphoviridae and Podoviridae families. One isolate, 6H, probably contains lipids as an essential virion component, based on its chloroform sensitivity and low buoyant density in CsCl. Each phage isolate rarely infected F. psychrophilum strains other than the strain used for its enrichment and isolation. Some bacteriophages could decrease mortality from intraperitoneal injection of its host strain when added together with the bacteria in a ratio of 10 plaque‐forming units per colony‐forming unit. While we recognize the artificial laboratory conditions used for these protection assays, this work is the first to demonstrate that phages might be able protect salmonids from RTFS or CWD.

Effect of fitness and physical activity on bone mass in adolescents: the HELENA Study - L. Gracia-Marco; G. Vicente-Rodríguez; J. A. Casajús; D. Molnar; M. J. Castillo; L. A. Moreno (European Journal of Applied Physiology, 2011)

Cadmium, copper, lead, and zinc in Mugil cephalus from seven coastal lagoons of NW Mexico - Martin G. Frías-Espericueta; J. Isidro Osuna-López; Martha A. Jiménez-Vega; Daniel Castillo-Bueso; Maria D. Muy-Rangel; Werner Rubio-Carrasco; Gabriel López-López; Gildardo Izaguirre-Fierro; Domenico Voltolina (Environmental Monitoring and Assessment, 2011)

Three thousand years of flank and central vent eruptions of the San Salvador volcanic complex (El Salvador) and their effects on El Cambio archeological site: a review based on tephrostratigraphy - D. Ferrés; H. Delgado Granados; W. Hernández; C. Pullinger; H. Chávez; C. R. Castillo Taracena; C. Cañas-Dinarte (Bulletin of Volcanology, 2011)

Sr, Nd and Pb isotopic and geochemical constraints for the origin of magmas in Popocatépetl volcano (central Mexico) and their relationship with the adjacent volcanic fields - Ignacio S. Torres-Alvarado; Alan D. Smith; José Castillo-Román (International Geology Review, 2011)

Neo-sex chromosome diversity in Neotropical melanopline grasshoppers (Melanoplinae, Acrididae) - Elio R. D. Castillo; Claudio J. Bidau; Dardo A. Martí (Genetica, 2010)

Shrub encroachment can reverse desertification in semi‐arid Mediterranean grasslands - Fernando T. Maestre; Matthew A. Bowker; María D. Puche; M. Belén Hinojosa; Isabel Martínez; Pablo García‐Palacios; Andrea P. Castillo; Santiago Soliveres; Arántzazu L. Luzuriaga; Ana M. Sánchez; José A. Carreira; Antonio Gallardo; et al. (Ecology Letters, 2009)
The worldwide phenomenon of shrub encroachment in grass‐dominated dryland ecosystems is commonly associated with desertification. Studies of the purported desertification effects associated with shrub encroachment are often restricted to relatively few study areas, and document a narrow range of possible impacts upon biota and ecosystem processes. We conducted a study in degraded Mediterranean grasslands dominated by Stipa tenacissima to simultaneously evaluate the effects of shrub encroachment on the structure and composition of multiple biotic community components, and on various indicators of ecosystem function. Shrub encroachment enhanced vascular plant richness, biomass of fungi, actinomycetes and other bacteria, and was linked with greater soil fertility and N mineralization rates. While shrub encroachment may be a widespread phenomenon in drylands, an interpretation that this is an expression of desertification is not universal. Our results suggest that shrub establishment may be an important step in the reversal of desertification processes in the Mediterranean region.

Strontium Levels in Different Causes of Death: Diagnostic Efficacy in Drowning - M. D. Pérez-Cárceles; A. Sibón; M. L. Gil del Castillo; M. A. Vizcaya; E. Osuna; T. Casas; J. L. Romero; A. Luna (Biological Trace Element Research, 2008)

Genetic erosion and in situ conservation of Lima bean (Phaseolus lunatus L.) landraces in its Mesoamerican diversity center - J. Martínez-Castillo; P. Colunga-GarcíaMarín; D. Zizumbo-Villarreal (Genetic Resources and Crop Evolution, 2008)

Immunological changes after a single bout of moderate-intensity exercise in a hot environment - J. Romeo; D. Jiménez-Pavón; M. Cervantes-Borunda; J. Wärnberg; S. Gómez-Martínez; M. J. Castillo; A. Marcos (Journal of Physiology and Biochemistry, 2008)

Digestive responses of two omnivorous rodents (Peromyscus maniculatus and P. alstoni) feeding on epigeous fungus (Russula occidentalis) - T. D’Alva; C. Lara; A. Estrada-Torres; C. Castillo-Guevara (Journal of Comparative Physiology B, 2007)

Plasma Zinc Concentration, Body Composition and Physical Activity in Obese Preschool Children - G. Weisstaub; E. Hertrampf; D. López de Romaña; G. Salazar; C. Bugueño; C. Castillo-Duran (Biological Trace Element Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Interactions Between Nitrate Assimilation and 2,4-Dinitrophenol Cometabolism in Rhodobacter capsulatus E1F1 - V.M. Luque-Almagro; R. Blasco; L. Paloma Sáez; M. D. Roldán; C. Moreno-Vivián; F. Castillo; M. Martínez-Luque (Current Microbiology, 2006)

Influence of thermal history on the response of Montastraea annularis to short-term temperature exposure - K. D. Castillo; B. S. T. Helmuth (Marine Biology, 2005)

The contribution of ancestry, chance, and past and ongoing selection to adaptive evolution - Amitabh Joshi; Robinson B. Castillo; Laurence D. Mueller (Journal of Genetics, 2003)

Investigation of Tuberculosis Contacts in a Nonhospital Pneumology Practice - D. del Castillo Otero; M. Peñafiel Colás; F. Álvarez Gutiérrez; J.G. Soto Campos; E. Calderón Osuna; J. Toral Marín; J. Sánchez Gómez (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Degradation of p -nitrophenol by the phototrophic bacterium Rhodobacter capsulatus - M. D. Roldán; R. Blasco; F. J. Caballero; F. Castillo (Archives of Microbiology, 1997)

Environmental preferences of yellowfin tuna ( Thunnus albacares ) at the northern extent of its range - B. A. Block; J. E. Keen; B. Castillo; H. Dewar; E. V. Freund; D. J. Marcinek; R. W. Brill; C. Farwell (Marine Biology, 1997)